Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Progotir Pathey, Bangladesh Multiple Indicator Cluster Survey 2019, Survey Findings Report - Bangladesh Bureau of Statistics (BBS); UNICEF Bangladesh (Bangladesh Bureau of Statistics (BBS), 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:GI5823C2 2339240:N5JK4A3G 2405685:2RPSQCKH 2405685:78ADZUUD

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Shohel, M. Mahruf C.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
The increasing use of media and technologies for enhancing teaching and learning is an important current trend to overcome the challenges of schooling and teacher training in the changing world. Many countries in the Global South are trying to adopt technologies in their school and teacher training systems to achieve the UN Millennium Development Goals. Though some recent research shows impacts of using technologies for enhancing teaching and learning in technology-poor contexts, no research actually addresses the challenges and difficulties associated with using the technologies in those specific contexts. This article presents interview data derived from secondary schools teachers in Bangladesh, in a context beset with many difficulties associated with technology use. In a pilot project, Apple iPods were introduced in 2009 to explore the challenges and consequences of using technology in schools. The data reveal the implications for the teachers’ professional development when they used the iPod as a multimedia player to access educational resources made available to support teaching and learning. This article has also thrown some light on current debates about using technologies for enhancing teaching and learning in technology-poor contexts.
KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2012.671177 10/gf5f6w 2339240:IVHSIR7Q 2405685:9ATXKXTE
Keywords: Bangladesh; THEME: Curriculum and resources; THEME: Open systems; THEME: Teacher Professional Development; _Source:Intuitive; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

Perception and Usage Level of ICT of the Primary School Teachers in Bangladesh - Mia, Abdul Hannan; Haque, Ziaul (Bangladesh Journal of MIS, 2013)
Bangladesh has been investing in the integration of information and communication technology (ICT) in education from the last decade. The evolution of the Information and Communication Technology (ICT) and their integration in the education lead to specific changes both in personal and professional area of primary school teachers in Bangladesh. Bangladesh has realized the need for a high quality primary education system and seen huge government funding for schools over the last 7years. However, Bangladesh’s spending on ICT has attracted little research regarding the impact of ICT on primary school teachers. For this reason, this study aimed to discover perception and usage level of ICT of the primary school teachers in Bangladesh. The study found that teachers have deficiency in usage and training of ICT. Findings revealed that programs on ICT provided for the primary schools in Bangladesh were too basic and that further investment is required. Data analyzed by STATA indicate that perception of primary school teachers about the ICT is positive irrespective of demographic characteristics such as sex, level of profession, type of institution, marital status and age. The usage level of ICT is not satisfactory whether the teacher is married or single, senior or junior or headmaster, male or female and government or non government. Some initiative can be taken to improve the ICT use among primary school teachers such as training on ICT, setup of computer Lab in primary school, introducing a course on ICT in primary level, reducing the cost of Internet connection and ICT devices etc.
KerkoCite.ItemAlsoKnownAs: 2339240:UBXB9GCB 2405685:B56Z8L24
Keywords: ⛔ No DOI found

A Theory of Change for Teachers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Ahmed, Shakil; Kaye, Tom; Zubairi, Asma (EdTech Hub, 2022)
The second of a trilogy of Theories of Change (TOCs) that focuses on teachers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how teachers’ professional learning experiences will enable them to support learners in ways that take advantage of available technology. The TOC is a useful tool to support the design, implementation, and evaluation of all programmes and initiatives that are designed for teachers, and aim to improve educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; teachers' professional development; education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6400980 10.53832/edtechhub.0086 10.53832/edtechhub.0088 2405685:29Z2JFJT 2405685:CB5GGAXU
Keywords: _r:AddedByZotZen

Artificial Intelligence in Education Across Bangladesh: Findings from a rapid scan and key informant interviews - Honda, Delanie; Ahmed, Shakil; Ramesh Vasudevan, Sharanya (EdTech Hub, 2025)
This Helpdesk Report was developed in response to a request from the UK's Foreign Commonwealth and Development Office (FCDO) Bangladesh for a rapid scan on the use of Artificial Intelligence (AI) in Bangladesh’s education system. The report aims to provide education decision-makers with accessible, evidence-based summaries of best practices in specific areas of EdTech, in this case, the AI landscape in Bangladesh. Using a combination of desk research and key informant interviews, the scan provides insights for the FCDO by highlighting key actors, early use cases, opportunities, and challenges, and to support future thinking about AI’s role in education, particularly as Bangladesh is preparing for its next development education plan — the Primary Education Sub-Sector Programme. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 16573142 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1133 ZenodoArchiveConcept: 16573141
Keywords: _r:AddedByMyEducationEvidence

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7054334 ZenodoArchiveConcept: 7054333 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7054334 10.53832/edtechhub.0126 2405685:GQSKFD62 2405685:XLXRPW3Z
Keywords: _r:AddedByZotZen

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5652015 KerkoCite.ItemAlsoKnownAs: 10.5281/edtechhub.0044 10.5281/zenodo.4610089 10.53832/edtechhub.0044 2339240:D4Q4RX94 2339240:YKVDDCEI 2405685:2T7DPIBU 2405685:BUHD2X9T 2405685:E4I95IWF 2405685:NP95DHA2 2405685:Q2MS5ZSE 2405685:ZSEHKGUN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

English language teaching in Bangladesh today: Issues, outcomes and implications - Rahman, Mohammad Mosiur; Islam, Md Shaiful; Karim, Abdul; Chowdhury, Takad Ahmed; Rahman, Muhammad Mushfiqur; Seraj, Prodhan Mahbub Ibna; Singh, Manjet Kaur Mehar (Language Testing in Asia, 2019)
Given the significance of English in the global world, English language teaching in Bangladesh has become subject to a supreme concern in maintaining economic growth and developing a skilled workforce. In this article, several barriers have been discussed based on a critical analysis of published materials. This review article covers several key issues such as the status of English in the country; English in education policies; factors affecting the implementation of communicative language teaching curriculum, method, and materials in Bangladesh; validity of the current assessment and its washback effect on English language teaching in Bangladesh; and current situation of teachers’ professional development. The article concluded with language policy and planning implications for policymakers, curriculum and material developers, public exams’ test-setters, and future English teacher training programmes, keeping the overall development of ELT in Bangladesh in mind.
KerkoCite.ItemAlsoKnownAs: 10.1186/s40468-019-0085-8 10/gg398d 2339240:6DJW9B5P 2339240:T5V5WJQJ 2405685:EH4KT3RK 2405685:VUKTNAHY

Parenting in Bangladesh: A Review of the Literature from 2006 to 2018 - Jasmine, Umme Habiba; Nduna, Mzikazi (Journal of Comparative Family Studies, 2022)
This study was a point of departure for future research on the need for a coherent understanding and knowledge of parenting in Bangladesh. This article presents the findings from an integrative research review on parenting in Bangladesh. A comprehensive search conducted in PubMed, Science Direct, and PsychINFO using the keywords “parenting”, “childcare”, “motherhood”, “fatherhood”, “mothering”, “fathering”, each paired with “Bangladesh” yielded 246 articles. Twenty papers published between 2006 and 2018 were selected for thematic analysis based on pre-set criteria. In most studies, the term mother was used interchangeably with parent, with mothers regarded as the primary caregiver. Parenting in the Bangladeshi context was found to be conceptualized primarily in terms of attitudes, disciplinary practices, feeding, parent–child interaction, and psychosocial stimulation. Parenting components aimed at moral development and attachment building in children were underrepresented. The data revealed largely inconsistent and uncoordinated discussions of parental practices, demonstrating the lack of a holistic approach in the literature in Bangladesh. Research on parenting in Bangladesh favors gendered assumptions of females as the primary caregiver. Based on their findings, the authors recommend qualitative studies to better reflect and conceptualize the concept of parenting in Bangladesh.
Publisher: University of Toronto Press KerkoCite.ItemAlsoKnownAs: 10.3138/jcfs-2021-0071 2339240:9PP366GD 2405685:WCUZM8QA
Keywords: Bangladesh; gendered role; integrative review; literature review; mother; mère; parentalité; parenting; revue de littérature; revue intégrée; rôle genré

E-Learning in Bangladesh: A Study of Teachers’ Behavioral Orientation and Affective Alignment in the Post-New Normal - Shamim Miah, A.S.M; Rasel Kabir, Md; Sultana, Sarmin (Contemporary Research in Education and English Language Teaching, 2020)
This study explores the teachers’ behavioral and affective orientation to e-learning that is in practice at all the levels of education in Bangladesh i.e. primary school, secondary school, higher secondary school, college, and university. By investigating the reasons for such disarray, it proposes solutions to overcome them. It acquired its data through online surveys followed by quantitative analysis through descriptive inferential analogies of the logarithmically represented findings. The result of the study documents that teachers’ preparation, technological know-how and adaptation to the e-learning platforms, their methods of teaching, measurement of outcomes, and mapping of curricula suggest that e-learning in Bangladesh is vitiated due to the diffusion in the teaching staff demographics and diluted apprehension of the e-learning. The paper’s primary findings show that Bangladesh’s progress from Education 1.0 to Education 3.0 is more affective and behavioral than cognitive in the implementation; wherein, the very concept of e-learning is diluted or spun around the idea of education via some usage of technology only, more specifically web conference applications which is indicative of Education 2.0 practices. There is no distinction made that separates online learning from e-learning, e-learning from distance and distance from blended learning, etc. in the current environment.
KerkoCite.ItemAlsoKnownAs: 10.33094/26410230.2020.21.16.35 10/gj37h5 2339240:A7RYDPHH 2405685:KVRAQU2P

Introducing mobile technology for enhancing teaching and learning in Bangladesh: teacher perspectives - Shohel, M. Mahruf C.; Power, Tom (Open Learning: The Journal of Open, Distance and e-Learning, 2010)
This paper reviews the themes emerging from Bangladeshi teachers’ experiences of taking part in the initial research and the development stage of a professional development programme they were involved with. The Secondary Teaching and Learning Programme is an information and communications technologies‐enhanced supported open distance learning programme of professional development in English‐language teaching. This paper presents evidence arising from semi‐structured interviews carried out with teachers from a pre‐pilot study for the English in Action project. The teachers participating in this study reflect upon six months’ experience of using professional development materials (course material of audio podcasts enhanced with text and images; videos of classroom practice; audio of classroom language) and classroom resources (audio recordings of text‐book reading passages, songs, poems and stories), all accessed via portable digital media players (iPods).
Publisher: Routledge _eprint: https://doi.org/10.1080/02680513.2010.511953 shortDOI: 10/brrchv KerkoCite.ItemAlsoKnownAs: 10.1080/02680513.2010.511953 10/brrchv 2405685:EEAEL6VW 2405685:UTNGW9R7
Keywords: Bangladesh; C:Bangladesh; English in Action support model; ___working_potential_duplicate; mobile learning; mobile technology; technology intervention

Introducing mobile technology for enhancing teaching and learning in Bangladesh: teacher perspectives - Shohel, M. Mahruf C.; Power, Tom (Open Learning: The Journal of Open, Distance and e-Learning, 2010)
This paper reviews the themes emerging from Bangladeshi teachers’ experiences of taking part in the initial research and the development stage of a professional development programme they were involved with. The Secondary Teaching and Learning Programme is an information and communications technologies‐enhanced supported open distance learning programme of professional development in English‐language teaching. This paper presents evidence arising from semi‐structured interviews carried out with teachers from a pre‐pilot study for the English in Action project. The teachers participating in this study reflect upon six months’ experience of using professional development materials (course material of audio podcasts enhanced with text and images; videos of classroom practice; audio of classroom language) and classroom resources (audio recordings of text‐book reading passages, songs, poems and stories), all accessed via portable digital media players (iPods).
Publisher: Routledge _eprint: https://doi.org/10.1080/02680513.2010.511953 shortDOI: 10/brrchv KerkoCite.ItemAlsoKnownAs: 10.1080/02680513.2010.511953 10/brrchv 2405685:EEAEL6VW 2405685:UTNGW9R7
Keywords: Bangladesh; C:Bangladesh; English in Action support model; ___working_potential_duplicate; mobile learning; mobile technology; technology intervention

Integrating ICT in English Language Teaching in Bangladesh: Teachers’ Perceptions and Challenges - Khan, Nafis Mahmud; Kuddus, Khushboo; Kuddus, Khushboo; School of Humanities (English), KIIT Deemed to be University, Bhubaneswar, Odisha, India. (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2020)
The integration of Information and Communication Technology (ICT) in Education especially, in English Language Teaching (ELT) in secondary schools of Bangladesh has been existing for a decade now. However, the status of actual implementation is quite different from the adoption and initiatives taken to integrate ICT in ELT. Therefore, the study aims to investigate the secondary level English language teachers’ attitude towards integration of ICT in Communicative Language Teaching (CLT) and the factors inhibiting the use of it. Further, the paper attempts to examine the challenges faced by the secondary level English teachers of Bangladesh in using ICT in language teaching effectively. In an attempt to examine the attitude of teachers in using ICT in ELT, a quantitative research is designed with a close ended questionnaire to collect the data from a sample of 100 secondary English language teachers of various schools of Bangladesh. The data of the responses is quantified and is analyzed by SPSS 20 program. The obtained data from the questionnaire is examined in order to investigate the perceptions of the secondary level English language teachers towards ICT integrated language teaching and the challenges of the implementation of ICT in ELT. In conclusion, the outcome of the research would provide significant information about the attitude of the teachers towards ICT integration in ELT and the challenges faced by them and hence, the study would help the policy makers and the teachers to enhance the effectiveness of using ICT in ELT.
KerkoCite.ItemAlsoKnownAs: 10.21659/rupkatha.v12n5.rioc1s23n1 10/gj37jk 2339240:C45NVN5G 2405685:7JJTNDXM

Compendium of Social Protection Research in Bangladesh - Government of Bangladesh (The General Economics Division (GED), Bangladesh Planning Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:L7AXVDVM 2405685:CJY2YG6P 4803016:G647E99W

Situation analysis on children with disabilities in Bangladesh 2014 - UNICEF (UNICEF Bangladesh, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:8PZV39B2 2405685:N5JYZLXV
Keywords: Bangladesh; Children with disabilities

Secondary Education During Lockdown Situation Due to Covid-19 Pandemic in Bangladesh: Teachers’ Response on Online Classes - Farhana, Z; Tanni, S; Shabnam, S; Chowdhury, S (Journal of Education and Practice, 2020)
Online classes started in many secondary schools one month after the compulsory closure of all education institutions in Bangladesh. This study explores the current scenario as well as challenges of adaptation of online classes in secondary education in terms of teachers’ experience. The study followed sequential exploratory mixed-method approach. Five secondary teachers were interviewed and 54 secondary teachers from 17 districts in Bangladesh were surveyed over telephone, Google forms and by email. The quantitative data was analyzed with Microsoft Excel and the thematic analysis approach had been followed for the qualitative one. The findings revealed that a good number of teachers have started teaching online by using social media platforms despite of not having any training or experience. Very few respondent teachers were found to take online examination; instead they are trying to assess the students from the feedback of given home works and home assignments. Teachers are facing numerous challenges like deficit of digital equipment, lack of expertise, unfamiliarity with the LMS, proficiency in assessment technique etc. The paper concludes with few recommendations such as providing proper devices to the teachers and students to participate in online class; facilitate rigorous training to enhance technology-based skills and capacities of the teachers so as to get the expected outcome.
KerkoCite.ItemAlsoKnownAs: 10.7176/jep/11-20-11 10/gj37h6 2339240:L9JH4WCG 2405685:3E5UXJXJ

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

How Bangladesh repurposed pre-existing online platforms to reimagine education during Covid-19 - Bangladesh), Anir Choudhury (a2i (EdTech Hub, 2021)
Forty-two million. That is the total number of students in Bangladesh. Forty-two million potential leaders of tomorrow. Forty-two million reasons to be hopeful for the country’s future. Forty-two million students who, because of Covid-19, were left without classrooms, without their friends, without their schools and colleges – without formal education.
KerkoCite.ItemAlsoKnownAs: 2405685:HVNU4INN 2405685:TA8WC382
Keywords: _EdTechHub_Output

TV-Based Learning in Bangladesh: Is it Reaching Students? - Biswas, Kumar; Asaduzzaman, T.M.; Evans, David; Fehrler, Sebastian; Ramachandran, Deepika; Sabarwal, Shwetlana (World Bank, 2020)
Is TV-based learning during COVID-19 school closures in Bangladesh reaching students? Most students (86 percent) within our sample of more than 2,000 Grade 9 stipend recipients are aware of government provided TV-based learning programs; yet only half of the students with access to these programs choose to access them. Also, very few students (21 percent) have access to government provided online learning programs, and among those that do, only about 2 percent choose to access them. There is a perceptible decline in the time students spend studying at home after school closures. This may be linked to the fact that 1 in 2 parents claim they are unable to help their children with new topics. Despite lower education, mothers are significantly more likely to be involved in the child’s education compared to fathers. Most students (90 percent) claim they have a supportive environment at home for studying. This is true for both boys and girls. Finally, nearly 65 percent of households in our sample report declines in income and 28 percent had to decrease the amount of food consumed within the household in the previous week.
KerkoCite.ItemAlsoKnownAs: 10.1596/34138 2339240:C5IHCNQD 2339240:IM47JZ2Z 2339240:M56ICKNT 2339240:SVXNVHB3 2405685:2NGQ3V9V 2405685:5SKQVXG9 2405685:F8Y2BXPY 2405685:HCD7DA27 2405685:XQXHTGSI 2534379:EBH9X23R
Keywords: Access to Education; Distance Learning; Education; Online Learning; School Closure; Secondary Education; ___working_potential_duplicate

Teachers’ professional development through the English in action secondary teaching and learning programme in Bangladesh: Experience from the UCEP schools - Shohel, M; Banks, F; Banks, F (Procedia - Social and Behavioral Sciences, 2010)
This paper explores the English in Action (EIA) intervention in Bangladesh and explores how the school-based support systems impact on classroom practice in Underprivileged Children’s Educational Programs (UCEP) Schools. It presents evidence to demonstrate how in-school training helps teachers’ professional development (TDP). This paper explores TPD by analysing interviews with UCEP school administrators and teachers who are participating in the pre-pilot EIA intervention. It draws a conclusion that school-based support systems combined with technology enhanced open and distance learning (ODL) are contributing significantly to TPD as an in-service training.
KerkoCite.ItemAlsoKnownAs: 10/bfg65g 2339240:M5TKZEV8 2405685:LQTN958P

Teachers’ professional development through the English in Action Secondary Teaching and Learning Programme in Bangladesh: experience from the UCEP schools - Shohel, M. Maruf C; Banks, Frank (Procedia-Social and Behavioral Sciences, 2010)
This paper explores the English in Action (EIA) intervention in Bangladesh and explores how the school-based support systems impact on classroom practice in Underprivileged Children’s Educational Programs (UCEP) Schools. It presents evidence to demonstrate how in-school training helps teachers’ professional development (TDP). This paper explores TPD by analysing interviews with UCEP school administrators and teachers who are participating in the pre-pilot EIA intervention. It draws a conclusion that school-based support systems combined with technology enhanced open and distance learning (ODL) are contributing significantly to TPD as an in-service training
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.sbspro.2010.03.894 2339240:WE7Z36DR 2405685:VDJRNRTI 2534378:A22MYIWP 2534378:HS2WT9YY 2534378:Q2THK4LH
Keywords: EiA Intervention; Experiential Learning; Secondary Teaching and Learning Programme; Teachers’ Professional Development; UCEP-Bangladesh; __:import:01; __:match:final; __:matched; __:study_id:2457264; __finaldtb

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Shohel, M. Mahruf C.; Kirkwood, Adrian (Learning, Media and Technology)
The increasing use of media and technologies for enhancing teaching and learning is an important current trend to overcome the challenges of schooling and teacher training in the changing world. Many countries in the Global South are trying to adopt technologies in their school and teacher training systems to achieve the UN Millennium Development Goals. Though some recent research shows impacts of using technologies for enhancing teaching and learning in technology-poor contexts, no research actually addresses the challenges and difficulties associated with using the technologies in those specific contexts. This article presents interview data derived from secondary schools teachers in Bangladesh, in a context beset with many difficulties associated with technology use. In a pilot project, Apple iPods were introduced in 2009 to explore the challenges and consequences of using technology in schools. The data reveal the implications for the teachers’ professional development when they used the iPod as a multimedia player to access educational resources made available to support teaching and learning. This article has also thrown some light on current debates about using technologies for enhancing teaching and learning in technology-poor contexts.
KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2012.671177 10/gf5f6w 2339240:FIJ742J6 2339240:IVHSIR7Q 2405685:957G58VG 2405685:9ATXKXTE
Keywords: Bangladesh; THEME: Curriculum and resources; THEME: Open systems; THEME: Teacher Professional Development; _Source:Intuitive; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Shohel, M. Mahruf C.; Kirkwood, Adrian (Learning, Media and Technology)
The increasing use of media and technologies for enhancing teaching and learning is an important current trend to overcome the challenges of schooling and teacher training in the changing world. Many countries in the Global South are trying to adopt technologies in their school and teacher training systems to achieve the UN Millennium Development Goals. Though some recent research shows impacts of using technologies for enhancing teaching and learning in technology-poor contexts, no research actually addresses the challenges and difficulties associated with using the technologies in those specific contexts. This article presents interview data derived from secondary schools teachers in Bangladesh, in a context beset with many difficulties associated with technology use. In a pilot project, Apple iPods were introduced in 2009 to explore the challenges and consequences of using technology in schools. The data reveal the implications for the teachers’ professional development when they used the iPod as a multimedia player to access educational resources made available to support teaching and learning. This article has also thrown some light on current debates about using technologies for enhancing teaching and learning in technology-poor contexts.
KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2012.671177 10/gf5f6w 2339240:FIJ742J6 2339240:IVHSIR7Q 2405685:957G58VG 2405685:9ATXKXTE
Keywords: Bangladesh; THEME: Curriculum and resources; THEME: Open systems; THEME: Teacher Professional Development; _Source:Intuitive; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

Making Vision 2041 a Reality: Perspective Plan of Bangladesh 2021-2041 - General Economics Division, Bangladesh Planning Commission, Ministry of Planning, Government of the People’s Republic of Bangladesh (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Z8H6NIQ8 2405685:KJM92W3X

Bangladesh: ensuring education for all Bangladeshis - World Bank (World Bank, 2016)
Bangladesh has made remarkable gains over the past two decades by ensuring access to education, especially at the primary level and for girls. The country’s net enrollment rate at the primary school level increased from 80 percent in 2000 to 98 percent in 2015.
KerkoCite.ItemAlsoKnownAs: 10/07/ensuring-education-for-all-bangladeshis 2339240:LV2HIFEQ 2405685:NEQZBPBW LV2HIFEQ
Keywords: Asia; South Asia

Digital in Bangladesh: All the Statistics You Need in 2021 - DataReportal (DataReportal – Global Digital Insights, 2021)
Our huge new collection of statistics and insights into how people in Bangladesh use the internet, social media, mobile, and ecommerce in 2021.
KerkoCite.ItemAlsoKnownAs: 2339240:I94ZZMY6 2339240:J4Q9N36L 2405685:3U3S5NRZ 2405685:G7IWS6TF 2405685:YVMDGILY 2534379:969KQJR3
Keywords: ___working_potential_duplicate

English in action: school based teacher development in Bangladesh - Power, Tom; Shaheen, Robina; Solly, Mike; Woodward, Clare; Burton, Sonia (The Curriculum Journal, 2012)
shortDOI: 10/gftr33 KerkoCite.ItemAlsoKnownAs: 10/gftr33 2405685:2298G5YZ
Keywords: C:Bangladesh

Bangladesh - Quality Learning for All Program for Results : Environmental and social system assessment (English) - World Bank (2018)
Bangladesh - Quality Learning for All Program for Results : Environmental and social system assessment (English)
KerkoCite.ItemAlsoKnownAs: 2339240:GMW5LP2I 2405685:555EASFK

EIA- A Teacher Education Project in Bangladesh: An Analysis from Diversified Perspectives - Karim, Abdul; Mohamed, Abdul Rashid; Prof., School of Educational Studies, Universiti Sains Malaysia, Malaysia, richsesusm@gmail.com; Rahman, Mohammad Mosiur; Graduate Research Student, School of Languages, Literacies and Translation, Universiti Sains Malaysia, Malaysia, mosiurbhai@gmail.com (International Journal of Instruction, 2017)
English in Action (EIA) is an ongoing teacher education project which places mobile technology at the centre of its action. Most of the studies carried out focused on the changes EIA brought in teachers’ classroom actions. Along with this, they also explored the classroom to observe whether the input given during training program is implemented in real life. No study has been conducted that compares and contrasts the components of mobile learning in general and the components EIA is using. This study, particularly, drew a comparative analysis between the mobile learning and EIA initiated mobile learning to reveal the extent it matched or mismatched to the components of mobile learning. It also scrutinized teachers’ behavior in the classroom after participating in EIA. It also penetrated to find the contents to be reviewed. Qualitative method was used to conduct this study. The result revealed that the components of EIA match to the mobile learning ones to the extent that EIA entails those suiting the context. Few elements were seemed absent as they are less suitable in such context. Besides, teachers were found bringing changes in their classrooms. The introduction of action research and reflective teaching were suggested to add to EIA’s program.
KerkoCite.ItemAlsoKnownAs: 10.12973/iji.2017.1044a 10/gj37f6 2339240:48HM2XCX 2405685:U36LAV2R

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Five lessons learnt from Bangladesh's experience responding to COVID-19 - Sarwar, Mohammad Afzal Hossain; Hossain, Iqbal; Kaye, Tom (EdTech Hub, 2020)
by Md. Afzal Hossain Sarwar (a2i), Iqbal Hossain (UNICEF Bangladesh) and Tom Kaye (EdTech Hub) In recent months, the EdTech Hub has produced a range of documents to support and guide countries as they develop and implement plans to help students keep learning during school closures. Some of the work we have produced includes: a guide to a five-part response…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707856 10.5281/zenodo.4707858 2339240:3JLSUFML 2339240:PISQI3AG 2405685:7G3XE8J6 2405685:HXB42AHC 2405685:PH8ICW77 2405685:RDMBW97E
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Bangladesh - Overview - World Bank (World Bank, 2021)
The International Development Association (IDA) has supported Bangladesh since 1972, just after the country’s independence. Since then, the World Bank through its concessional lending arm has committed nearly $26 billion in grants and interest-free credits to Bangladesh.
KerkoCite.ItemAlsoKnownAs: 2339240:9GAMGSVG 2405685:RUP3LCB2

Challenges and Developments in the Higher Education System of Bangladesh: Keys to Way Forward - Chowdhury, Mahfuzul Hoque; Absar, Mir Mohammed Nurul; Quader, Syed Manzur (Handbook of Education Systems in South Asia, 2020)
Series Title: Global Education Systems KerkoCite.ItemAlsoKnownAs: 10.1007/978-981-13-3309-5_57-1 2339240:GB9KNSCS 2405685:WA9WN3R2

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7591685 ZenodoArchiveConcept: 7591684 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7591685 10.53832/edtechhub.0146 2405685:J8IB7LVG 2405685:V4EVQ39I
Keywords: _r:AddedByZotZen

English in action: school based teacher development in Bangladesh - Power, Tom; Shaheen, Robina; Solly, Mike; Woodward, Clare; Burton, Sonia (The Curriculum Journal, 2012)
shortDOI: 10/gftr33 KerkoCite.ItemAlsoKnownAs: 10.1080/09585176.2012.737539 10/gftr33 2339240:VTZ8NAVX 2405685:2298G5YZ 2405685:U3Z382B7
Keywords: Bangladesh; C:Bangladesh; English in Action; School Based Teacher Development; technologies

Bangladesh - World Inequality Database (WID - World Inequality Database, 2021)
Bangladesh The source for global inequality data. Open access, high quality wealth and income inequality data developed by an international academic consortium.
KerkoCite.ItemAlsoKnownAs: 2339240:QDDJSFXN 2405685:NF7Q3FVW

A Quasi-Experimental Study of the Classroom Practices of English Language Teachers and the English Language Proficiency of Students, in Primary and Secondary Schools in Bangladesh - Power, Tom; McCormick, Robert; Asbeek-Brusse, Elsbeth (2017)
English in Action (EIA) is an English language teacher development project based in Bangladesh that was intended to run from 2008 to 2017, but which was extended at the request of the Government of Bangladesh, with additional funding from UKAID, for a further year to 2018. By the time of the design of this study (2014-2015) EIA was drawing to the end of upscaling (phase III, 2011-2014) and entering institutionalisation and sustainability (phase IV, 2014-17, extended 2018). Successive prior studies had indicated substantial success in improving both teachers’ classroom practices and student learning outcomes, over the pre-project baseline (e.g. EIA 2011, 2012). The 2014 Annual Review of EIA recommended that in the final phase, EIA should explore whether it would be possible to carry out a study that compared a ‘counterfactual’ or control-group of teachers and students, to the ‘EIA’ or treatment schools: i.e. a Randomised Control Trial or Quasi-Experimental study. A proposal for a Quasi-Experimental study was developed in collaboration with DFID’s South Asia Research Hub (SARH), which also provided the additional funding necessary to implement such a study. The teachers and students who were the subject of this study, were the fourth cohort to participate in English in Action (together with teachers from ‘control’ schools, in the same Upazilas). This fourth EIA cohort included Schools, Teachers and Students from approximately 200 Upazilas (of approximately 500 in total) across Bangladesh, including some of the most disadvantaged areas (with reference to UNICEF deprivation index), such as Char, Hoar and Monga districts. Teachers took part in a school-based teacher development Programme, learning communicative language teaching approaches through carrying out new classroom activities, guided by teacher development videos that showed teachers, students and schools similar to those across the country. Teachers also had classroom audio resources for use with students. All digital materials were available offline, on teachers own mobile phones, so there is no dilution of the Programmes core messages about teaching and learning, by some intermediary coming between the teacher and the materials. Teachers were supported through these activities, by other teachers in their schools, by their head teachers and by local education officers. Some teachers from each area were also given additional support and guidance from divisional EIA staff, to act as Teacher Facilitators, helping teachers work through activities and share their experiences at local cluster meetings. Whereas previous cohorts of teachers had attended eight local teacher development meetings over their participation in the project, for Cohort Four, this was reduced to four meetings, with a greater emphasis being placed on support in school by head teachers, as well as support from local education officers. This change was part of the move towards institutionalisation and sustainability of project activities within and through government systems and local officers. The purpose of this study was both to provide the evaluation evidence required for the final phase of the EIA project and to contribute to the international body of research evidence on effective practices in teacher development in low-to-middle income country contexts.
Place: Dhaka, Bangladesh Publisher: English in Action (EIA) KerkoCite.ItemAlsoKnownAs: 2339240:5ASMY75P 2405685:GJV2BMAG

COVID-19 and Bangladesh: challenges and how to address them - Anwar, Saeed; Nasrullah, Mohammad; Hosen, Mohammad Jakir (Frontiers in Public Health, 2020)
As the coronavirus outbreak quickly surges worldwide, many countries are adopting non-therapeutic preventive measures, which include travel bans, remote office activities, country lockdown, and most importantly, social distancing. However, these measures face challenges in Bangladesh, a lower-middle-income economy with one of the world's densest populations. Social distancing is difficult in many areas of the country, and with the minimal resources the country has, it would be extremely challenging to implement the mitigation measures. Mobile sanitization facilities and temporary quarantine sites and healthcare facilities could help mitigate the impact of the pandemic at a local level. A prompt, supportive, and empathic collaboration between the Government, citizens, and health experts, along with international assistance, can enable the country to minimize the impact of the pandemic.
KerkoCite.ItemAlsoKnownAs: 10.3389/fpubh.2020.00154 2339240:Q8J6VE8P 2405685:6JBHGPXJ

Students perception of mobile learning during COVID-19 in Bangladesh: university student perspective - Biswas, Bikram; Roy, Sajib Kumar; Roy, Falguni (Aquademia, 2020)
The aim of this study is to measures the student’s perception of using mobile for learning during COVID-19 in Bangladesh especially at the university student’s perspective. During the COVID-19 pandemic period, mobile learning may help the students to fulfill the study gap. Due to COVID-19 pandemic 213 countries, higher education has affected all over the world of June 2020. Although all of the developed countries considered mobile learning as an effective tool for education, it is not used properly in Bangladesh. This survey method conducted on 416 students from different university students in Bangladesh to understand the student’s perception of using mobile phones as a learning system. The findings of this study show that most of the students at the university level have a positive perception of m-learning. This study revealed that m-learning is very helpful to recover the study gap during this COVID-19 pandemic time and the findings of this study will help the education policymaker as well as the educational institutions to incorporate mobile learning technology for the whole system where social media may enhance the process of teaching and learning.
Publisher: Veritas Publications LTD KerkoCite.ItemAlsoKnownAs: 10.29333/aquademia/8443 2339240:KHZM9M89 2405685:RBZUY224

Dynamics of Public Policy: Determinants of Policymaking and Implementation in Bangladesh - Aminuzzaman, S (Public Organization Review, 2013)
Socio-economic development achievements in Bangladesh have been characterized as a development paradox. The policymaking process in Bangladesh is seen as the outcome of incentives created by patronage politics as opposed to the compulsion for the government to play an effective developmental role. A number of factors strongly affect the public policy formulation and implementation process—factors such as the assistance and extent of pressure and persuasion from international development partners, and the capacity to mobilize and manage resources. The political commitment at the highest level is found to be the most critical determinant element of policy formulation and implementation in Bangladesh.
KerkoCite.ItemAlsoKnownAs: 10.1007/s11115-013-0262-7 10/gkm64h 2339240:989ZEISW 2405685:SG2Z636R

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6942540 10.53832/edtechhub.0103 2339240:Y9SQVEU9 2405685:77665EVG 2405685:JV4F45P5
Keywords: _r:AddedByZotZen

Introducing ICT into Teacher-Training Programs: Problems in Bangladesh - Khan, Shahadat Hossain; Hasan, Mahbub (Journal of Education and Practice, 2013)
Information and Communication Technology can offer more adaptable and efficient ways of teacher training for improvement of quality of professional development programs. But the use of ICT into teacher training usually faces certain obstacles. In this paper, we identified different barriers of introducing ICT into teacher training model (this model had been discussed by the authors in a separate paper, titled as “A model for integrating ICT into teacher training programs in Bangladesh based on TPCK) in Bangladesh, a developing country. We then described the strategies to overcome these problems for improving the current status of ICT integration into teacher training. Finally, we concluded with emerging research issues and offered pertinent recommendation with respect to ICT integration into teacher training program for improving quality of teaching in Bangladesh.
KerkoCite.ItemAlsoKnownAs: 2339240:JV86HLB6 2405685:L7TKD9JC
Keywords: ⛔ No DOI found

Bangladesh Population (2021) - Worldometer (2021)
Population of Bangladesh: current, historical, and projected population, growth rate, immigration, median age, total fertility rate (TFR), population density, urbanization, urban population, country's share of world population, and global rank. Data tables, maps, charts, and live population clock
KerkoCite.ItemAlsoKnownAs: 2339240:6KUWCRCQ 2405685:2LS69KMG

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Mahruf, C.; Shohel, M.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
Extra URL: https://www.tandfonline.com/doi/full/10.1080/17439884.2012.671177 KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2012.671177 10/gf5f6w 2339240:95DVIPCS 2339240:IVHSIR7Q 2405685:NXQEUUZM 2534378:CSPF7NEB 2534378:MLD48MMR 2534378:UQYRQ249
Keywords: BANGLADESH; Bangladesh; COMPUTER assisted instruction; COMPUTERS in education; CONTINUING education; DEVELOPING countries; EDUCATIONAL technology; INFORMATION technology; PROFESSIONAL education; SECONDARY school teachers; TEACHER development; TEACHERS – In-service training; _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Open systems; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2096535; __finaldtb; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

Teacher Training Program through Distance Education in Bangladesh Open University: The Challenges of Using ICT - Talukder, M (St. Theresa Journal of Humanities and Social Sciences, 2015)
Bangladesh Open University is the only public university in the country that imparts education in an open and distance mode. Since the establishment of this university in 1992, it has been providing teacher education and training throughout Bangladesh. Teaching is one of the most challenging professions today in Bangladesh where knowledge is expanding rapidly and modern technologies are attracting teachers to learn how to use these technologies in their teaching. Hence, the demand of teacher training is increasing day by day. Since teacher training program is an important issue in Bangladesh, it could be done through distance education using Information and Communication Technology (ICT). The present study attempts to find out the challenges of using ICT in teacher training program and provides a possible solution to it. A mixed-method approach was adopted by using a questionnaire, observation and semi-structured interviews with the faculty members of BOU. The findings show that, when teacher training program integrates ICT, it encounters a challenging operational environment – curriculum, skilled people, and infrastructures of the university, limitation of time and cost of the program.
KerkoCite.ItemAlsoKnownAs: 2339240:8UTGMBWB 2405685:INU9GQQU
Keywords: ⛔ No DOI found

The Issues and Challenges of Using Multimedia at a District Level, Specialized Girls’ College in Bangladesh - Sarowardy, Muhammad Hasan; Halder, Deb Proshad (Creative Education, 2019)
The use of multimedia in imparting education has inevitably been trendy owing to its multifold benefits which have been established and reinvestigated as inseparable teaching aid and tool in teaching-learning process. But This technological assisting component cannot be accorded in many of the institutions of Bangladesh due to several internal as well as external factors. This paper aims to highlight the emerging factors that beset in the institution of Bangladesh. This institutional study on the issues and challenges of using of multimedia in a district (urban area) level girls’ college projects a thorough realization of the difficulties what this types of attributive colleges face in Bangladesh. The resource constraint, the lack of motivation of the teachers, the lack of expert human resource, the insufficient digital tools and lack of multimedia-enabled class environment are found to be barriers and some guiding directives are also imposed in this paper that emerges through the interviews of the teachers and the Vice principal. Thus, the paper, in a miniature effort, tries to lay out the challenges the college of Bangladesh faces and highlight some remedial ways to cope up the challenges.
KerkoCite.ItemAlsoKnownAs: 10/gj37jg 2339240:M5B3GAH9 2405685:LDBLDTX5

Dynamics in Management of Open Schooling: a case of Open School of Bangladesh Open University - Alam, Shafiul; Rahman, M (2010)
The Open School (OS) of Bangladesh Open University (BOU) runs three pre-University programs namely Junior School Certificate (JSC) for Grade 6-8, Secondary School Certificate (SSC) for Grade 9-10, and Higher Secondary Certificate (HSC) for grade 11-12 through open and distance learning (ODL) mode. Management of these programs is highly influenced by the government policy particularly at the time of political change in Bangladesh. Normally, formal school syllabus and curriculum are subject to change as per the wills of the current government although BOUOS has the autonomy to design its curriculum. This change affects total management of open school because BOU Open School also maintains the curriculum for its school programs which is at par to the formal curriculum. This discusses the dynamics of open school management at the time of educational policy change in Bangladesh.
KerkoCite.ItemAlsoKnownAs: 2339240:S7IUXWG8 2405685:3KB7XYCF
Keywords: ⛔ No DOI found

Artificial Intelligence for Education in Bangladesh: Insights from the First Small-Scale Artificial Intelligence Needs Assessment and Training for Primary Education Teachers - Kong, Byeongjo; Li, Zhigang; Ratner, Sara; University of Oxford; Hemberg, Erik; AnyScale Learning For All; Haque, A. K. M. Shamsul (Asian Development Bank, 2024)
Bangladesh, with one of the largest education systems in the world, has started to lay the foundation for reskilling its youth in preparation for an automated world of work. The country has thus looked to using artificial intelligence (AI) in the education sector, recognizing its promise to transform the teaching–learning landscape while acknowledging the challenges inherent in its adoption. This paper presents results of an AI needs assessment survey and training workshop conducted among primary education teachers from 2023 to 2024, to gather opinions on pedagogies that could benefit from AI-enabled automation, as well as understand respondents’ perceptions of integrating AI and automation into their teaching tasks.
KerkoCite.ItemAlsoKnownAs: 10.22617/WPS240575-2 2339240:AI447E4V 2405685:GFCNWNN6

School drop out in Bangladesh: insights using panel data - Sabatés, Ricardo; Hossain, Altaf; Lewin, Keith M. (International Journal of Educational Development, 2013)
This paper examines the relative strength of different factors associated with school drop out using data collected between 2007 and 2009 in Bangladesh. A sample of 9046 children, aged 4-15, was selected across six districts for a household survey focusing on children's school access and experiences. Two groups of children were identified: those who were enrolled in school in both 2007 and 2009 and those who dropped out by 2009. Using a multivariate logit model, results show age and gender, together with financial constraints, such as lack of income and school expenditure, as the top predictors of school drop out. Two other important predictors are lack of parental support for children's school work and school absenteeism. This paper identifies some possible interventions that could reduce school drop out. These include campaigns to reduce late entry and overage enrolment, reductions in direct costs of schooling, and more support for low achieving children to compensate for lack of educational support at home.
Accepted: 2016-12-19T10:39:39Z Publisher: © 2012 Elsevier Ltd. KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2012.09.007 2339240:DQCCLUX4 2405685:JWHUF3GA

Household Income and Expenditure Survey 2016-2017 - Bangladesh Bureau of Statistics (Bangladesh Bureau of Statistics)
KerkoCite.ItemAlsoKnownAs: 2339240:UZ637S8G 2405685:CVHPT3RW 2405685:XH9PM5DE 2534379:WFZV8JAD
Keywords: ___working_potential_duplicate

Factors Affecting Higher Education Quality in Bangladesh: An Attempt to Improve Higher Education Quality in Bangladesh through HEQEP. - Hossain, Md (International Journal of Science and Business, 2017)
To meet the globalization challenges raising higher education quality to the world standard is essential. Because Economic Factors, An Era of Competition, Demographic Realities, lack of infrastectural development ,Governmental Political and Legal Challenges, Religious Factors, internal conflicts among educational institutions, corruption etc affect quality of higher education in Bangladesh. Bangladesh Govt. has taken initiatives to develop the quality of tertiary education. Govt. plans to prepare university graduates in such way that they can successfully compete in the context of international knowledge society. The Government prepared a Higher Education Strategic Plan 2006-26, which was fully homegrown with participation of front-line academics from both public and private universities and representatives from think-tanks and the private sector. Accordingly, the Ministry of Education, with the assistance of the World Bank, has undertaken a Higher Education Quality Enhancement Project (HEQEP). The project aims at improving the quality of teaching-learning and research capabilities of the tertiary education institutions through encouraging both innovation and accountability and by enhancing the technical and institutional capacity of the higher education sector. he Higher Education Quality Enhancement Project (HEQEP) will comprise of the following 4 (four) components: (i) promotion of academic innovation in teaching-learning and research through an Academic Innovation Fun (AIF) allocating funds on a competitive basis to public and private universities; (ii) institutional capacity building at the University Grants Commission (UGC) and the universities; (iii) connectivity capacity building for universities and research centers through the development of the Bangladesh Research and Education Network (BdREN) ; and (iv) support to the operation of the project implementation unit. The University Grants Commission of Bangladesh is the implementing agency of the project. A HEQEP Unit has been established in UGC for implementation, management, monitoring and evaluation of the activities.
KerkoCite.ItemAlsoKnownAs: 2339240:4ZQMXJ4E 2405685:NVSTLUHE
Keywords: ⛔ No DOI found

Use of ICT by Biology Teachers in the Secondary Schools: Bangladesh Perspective - Farhana, Z; Chowdhury, S (Journal of Culture, Society and Development, 2019)
Information and communication technologies (ICT) have changed the pedagogy in education offering more student-centered learning incidents. The purpose of this study was to evaluate the use of ICT by the biology teachers in teaching-learning process of secondary schools in Bangladesh. A total of 50 biology teachers from several secondary schools of Bangladesh participated in the study. It was found that teachers have better access to computer than the average populace of Bangladesh. They have working knowledge on Microsoft Office Word, Excel, Power Point, and different web browsers. A good number of the teachers use computer for preparing their lectures, use internet for accessing educational materials, takes classes with multimedia with the support of ICT. However, about 17% to 25% were found to be not using these ICT means. Many teachers opined that they have less number of computers in the school to prepare for class work. They also assessed that hardware troubleshooting, software malfunction and unexpected power failure as challenges for using ICT. This paper recommends to provide continuous in-servicing training on ICT, interest free loan to teachers for purchasing laptop computer and to ensure technical support to overcome software and hardware problems in the schools.
KerkoCite.ItemAlsoKnownAs: 10.7176/jcsd/45-05 10/gj37jj 2339240:R2I6C4KK 2405685:8YK9A8A2

Usage level and Attitude of The Secondary Level Teachers' in Bangladesh Towards ICT at Personal and Professional Arena - Kashem, Abul; Haque, Ziaul (2014)
Integration of information and communications technologies (ICTs) in education sectors is one of the prime objectives of Bangladesh from the last decade. This study is conducted to assess the level of using ICT and acceptance of new technology by secondary level teachers in Bangladesh in their professional and personal arena. The study revealed that in Bangladesh most of the secondary level teachers use computer and internet for their personal purpose and use computers 35 times in a day. It revealed that secondary level teachers are interested to spend for ICT purpose. It also revealed that there is a difference in ICT usage between male and female teachers but no difference of the same among the different level of the teachers. It was found that there is no difference in case of perception about ICT between male and female teachers but perception among different level of teachers about ICT is different. Unavailability of high speed and wireless connections, lack of computer knowledge, high cost at start-up and unwillingness of aged teachers are found as hindrance for use of ICT in secondary level teaching arena. The success of information and communications technology (ICT) applications in teaching is profoundly dependent on the level of computer use by secondary level teachers. Majority of the Secondary level teacher were interested to accept the new technology for their professional capability enhancement and serve the nation. This questionnaire-based study assessed the level of computer and internet use by Secondary level teacher in Bangladesh is not satisfactory but perception of secondary level teacher for accepting new technology is positive both in their personal and professional arena.
KerkoCite.ItemAlsoKnownAs: 2339240:E889VQ5E 2405685:FN9HP3MF
Keywords: ⛔ No DOI found

Examining the Impact of an English in Action Training Program on Secondary-School English Teachers’ Classroom Practice in Bangladesh - Karim, Abdul; Mohamed, Abdul (The Qualitative Report, 2019)
English teachers in Bangladesh have undergone numerous training programs. Both government-initiated and donor-sponsored training programs have been in operation in Bangladesh. Government initiated institutions to train teachers are Primary Training Institutes (PTIs) and Teacher Training Colleges (TTCs). However, researchers seemed to label training provided by PTIs and TTCs as inadequate. Bridging the gaps intrigued government of Bangladesh to devise donor-aided training programs, including English Language Teaching Improvement Project (ELTIP), English for Teaching, Teaching for English (ETTE), Secondary Education Quality and Access Enhancement Project (SEQAEP), Teaching Quality Improvement in Secondary Education Project (TQI-SEP). Studies reported their potential failure to bring changes in English teachers’ classroom practices. English in Action (EIA) was the last donor-funded project that incorporated schoolbased training program. The aim of the study was to examine the impact of EIA training program on secondary-school English teachers’ classroom practice in Bangladesh, drawing the questions in relation to the elements learned in the training program and the elements practiced in the training program. The present study undertook the Integrated Approaches to Teacher Development suggested by Hargreaves and Fullan (1992) and Reflective Model developed by Wallace (1991). This study adopted phenomenological approach since it subsumed the experience of an activity or concept from the participants’ perspective. Eight Participants were selected who had been trained from EIA training program and who had experience of participating in other donor-aided program, in the spirit of yielding the uniqueness of EIA which informed the sustainability of this program. It had been divulged that teachers learned a lot of activities that were related to English language teaching. However, the present studies observed limited practice of such activities in the classroom.
KerkoCite.ItemAlsoKnownAs: 10/gj37h4 2339240:A6YSCF88 2405685:FPNL6NJJ

Innovative Delivery of Education in Bangladesh Using Mobile Technology - Cristol, Dean; Abdulbaki, Anwar; Tuhin, Salah Uddin; Al-Sabbagh, Samah; Majareh, Maryam; Gimbert, Belinda (2019)
Given the increasing use and accessibility of mobile technology, a pilot study, “Innovative Delivery of Education in Bangladesh Using Mobile Technology” was carried out using mobile learning devices to both increase and enrich the delivery of educational services in a remote Bangladesh district. The APTUS system was used to allow learners’ connection to digital learning platforms and content without electricity or internet access. The researchers maintained that mobile learning associated with Project Based Learning can effect student learning in five ways: (1) contingent learning, changing experience students have by responding to the environment; (2) situated learning, in which learning occurs in the conditions applicable to the learning; (3) authentic learning connected to immediate learning goals; (4) context-aware learning, in which the environment and history affect learning; and (5) personalized learning. The results from this pilot research study provides evidence of the students achievement growth overtime and motivated to learn higher-order thinking technology enhanced skills when practical applications are supplemented with technology tools such as tablets. Students reported a heightened interest in science as a result of the project. Teachers maintained that their teaching skills were enhanced by the project and able to apply practical applications to teach science rather than lecturing and rote learning. Parents attributed the project for their children being more motivated to learn science inside and outside of the classroom. The study appears to have a positive impact on the three groups of the participants and should be scaled up to benefit more learning communities, especially in remote areas of Bangladesh.
KerkoCite.ItemAlsoKnownAs: 2339240:UXGNF73S 2405685:MVSQSM9B
Keywords: ⛔ No DOI found

Mathematics Education and Accessible Technologies for Visually Impaired Students in Bangladesh - Nahar, L; Jaafar, A; Sulaiman, R (Badioze Zaman H. et al. (eds) Advances in Visual Informatics. IVIC 2017. Lecture Notes in Computer Science, vol 10645, 2017)
The learning process for the visually impaired students (VIS) is complicated because they are unable to get visual information. A lot of challenges and problems these VIS are facing to get education, especially in studying Mathematics. As a developing country, Bangladesh cannot afford for the costly Mathematics learning tools for VIS. The objective of this study is to analyze the current scenarios of learning Mathematics in different types of blind schools in Bangladesh. A survey is conducted in all three types of schools in order to achieve the objective. The survey was based on questionnaire comprising questions related to Mathematics learning, examination methods and learning difficulties. Survey results shows that they follow Braille system for reading and writing; however, they cannot write in Braille in the final examination. Taylor frame and abacus are the only options for counting numbers. This paper also tries to propose some key points to improve the current Mathematics learning process for the blind students.
KerkoCite.ItemAlsoKnownAs: 2339240:S7ZDF3ZX 2405685:FU3UTF9E
Keywords: ⛔ No DOI found

Investigating the mediating role of online learning motivation in the COVID-19 pandemic situation in Bangladesh - Rahman, Md. H Asibur; Uddin, Mohammad Shahab; Dey, Anamika (Journal of Computer Assisted Learning, 2021)
The purpose of this paper is to investigate the mediating role of online learning motivation (OLM) in the COVID-19 pandemic situation in Bangladesh by observing and comparing direct lectures (DL), instructor–learner interaction (ILI), learner–learner interaction (LLI), and internet self-efficacy (ISE) as predictors of OLM and online learning satisfaction (OLS). Data were collected from 442 undergraduate and graduate students from more than 35 universities in Bangladesh. To test the hypotheses, the PLS-SEM approach was applied using SmartPLS 3.0. The study shows a significant mediating role of OLM between the independent variables and learning satisfaction. In addition, DL, ILI, and ISE are shown to be significant predictors of student satisfaction. The findings have a number of valuable implications for education policy makers, universities, instructors, and students. Moreover, the study suggests some new research perspectives to overcome the limitations of this research and to gain precise knowledge on students' learning motivation and satisfaction regarding other online classes for different categories of students (e.g., high school and college, professional, and PhD).
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/jcal.12535 KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12535 2339240:D2LCXIHU 2405685:DUEDNPFM
Keywords: Bangladesh; COVID-19; interactions; learning motivation; learning satisfaction; online education

A conceptual framework of virtual interactive teacher training through open and distance learning for the remote areas english teachers of bangladesh - Parvin, Irene (Turkish Online Journal of Distance Education, 2017)
Since we are living in the information age and the importance of the need for communication among people of different cultures is increasing day by day in the globalizing world, people need to learn the languages of different cultures, particularly English, which is the common language of this global communication. This need for learning English requires trained qualified teachers of English. A scan of those who are teaching English in schools of Bangladesh reveals that most of them are very limited in both English skills and teaching methodologies for English. This situation is exacerbated when one moves into the rural areas. Most of the teachers are staying far away from the teachers’ training colleges and also for different constraint like administrative, financial, time constraint and were also unable to receive any training due to family problems. So Distance Education has a great demand to them. ICT is an effective media of distance education. For many years, universities with a significant commitment to distance and open education institutions have been at the forefront of adopting new technologies to increase access to education and training opportunities. Information and Communications Technology (ICT) is an umbrella term that includes all technologies for the manipulation and communication of information. Bangladesh Open University (BOU) is till now belonging to the second generation of distance education model but due to the enhancement of technology in Bangladesh, BOU can proceed further. The main purpose of this study is to identify a suitable technology for developing a virtual interactive teachers’ training program for the disadvantaged English teachers of Bangladesh. Respondents were selected through random sampling and data were analyzed using both descriptive statistics and quantitative themes. From the opinion of the secondary English teachers their access and acceptability on ICT was identified and also a need analysis was done. It is hoped that the result of this study will encourage the policy makers to implement new ODL approaches for the training of disadvantaged rural English teachers.
KerkoCite.ItemAlsoKnownAs: 10.17718/tojde.285813 10/gkm637 2339240:B2I9JZNJ 2405685:Q55R8HVA

An interactive math braille learning application to assist blind students in Bangladesh - Nahar, L; Sulaiman, R; Jafaar, A (Assistive Technology, 2020)
Due to the lack of affordable assistive tools for learning mathematics, blind students in Bangladesh still use outdated learning tools like Tailor Frame. Therefore, demand for a low-cost technological tool is there that will help the blind students to learn math braille and calculate numbers more easily. To provide an effective and affordable assistive tool, this study begins with a needs assessment study to identify the basic needs of blind students in learning math braille and solving mathematical calculations. Afterward, a mobile phone based interactive assistive application is proposed to improve the learning facilities of math braille using Nemeth code for blind students in Bangladesh. Interfaces of the application are designed based on their needs. Besides, interaction methods (such as, hearing & touching) of blind students with the physical world were another criterion in designing very interactive interfaces that provide self-learning facilities. The interfaces are evaluated by the teachers, experts, and end users in order to identify the usability. The evaluation shows a promising result toward the acceptability of the designed application. Therefore, this application can be helpful for the blind students to learn math braille using Nemeth Code.
KerkoCite.ItemAlsoKnownAs: 10.1080/10400435.2020.1734112 10/gkm64j 2339240:9H367DU5 2405685:9SMEBFMC

The Teachers’ Portal as a Tool for Teachers’ Professional Development in Bangladesh - Prime Minister's Office: Bangladesh (Access to Information Programme: Government of the People's Republic of Bangladesh; UNDP; USAID)
KerkoCite.ItemAlsoKnownAs: 2339240:HDPB587M 2405685:WVA2A26F

M-learn lessons learnt: Bangladesh perspective - Imam, Zaki (QScience Proceedings, 2013)
M-learning is a form of distance learning in that it provides a communication tool( the mobile phone) to bridge the distance between the providing institution and the learners and facilitates 2-way (synchronous and asynchronous) interactivity between teacher and the learner (McWilliams et al, 2007). M-learning allows the remote teachers to stay in frequent contact with teacher educators, to ask questions and discuss issues as they adapt new teaching practices. This programme has been initiated by Ministry of Education upon requested by ADB, Manila to implement technology based training programme for reaching remote and disadvantaged areas. M learning has been piloted by teacher educators of Government Teachers’ Training College in one district (Barisal, located in the southern part of Bangladesh) and later extended to four districts to train teachers of remote schools of Patuakhali, Sandwip, Hatya and Thakurgaon districts. Regular 14 day and 5 day follow-up face-to-face inservice Continuing Professional Development (CPD) training was adapted as a two day face-to-face orientation, followed by a 6 week programme with regular conference calls to support classroom practices. Findings of the programme are very promising for adapting new practices. The CPD training by using mobile phone became very successful for increasing teachers and student’s competence level. Government of Bangladesh and Development Partners are very keen to maximize the use of technology in CPD for teachers especially for addressing female teachers and reaching training facilities to remote areas.
KerkoCite.ItemAlsoKnownAs: 10.5339/qproc.2013.mlearn.24 10/gj37jm 2339240:A9MNH3VF 2405685:DA3TGYS8

Design of a Braille Learning Application for Visually Impaired Students in Bangladesh - Nahar, Lutfun; Jaafar, Azizah; Ahamed, Eistiak; Kaish, A. B. M. A. (Assistive Technology, 2015)
Visually impaired students (VIS) are unable to get visual information, which has made their learning process complicated. This paper discusses the overall situation of VIS in Bangladesh and identifies major challenges that they are facing in getting education. The Braille system is followed to educate blind students in Bangladesh. However, lack of Braille based educational resources and technological solutions have made the learning process lengthy and complicated for VIS. As a developing country, Bangladesh cannot afford for the costly Braille related technological tools for VIS. Therefore, a mobile phone based Braille application, “mBRAILLE”, for Android platform is designed to provide an easy Braille learning technology for VIS in Bangladesh. The proposed design is evaluated by experts in assistive technology for students with disabilities, and advanced learners of Braille. The application aims to provide a Bangla and English Braille learning platform for VIS. In this paper, we depict iterative (participatory) design of the application along with a preliminary evaluation with 5 blind subjects, and 1 sighted and 2 blind experts. The results show that the design scored an overall satisfaction level of 4.53 out of 5 by all respondents, indicating that our design is ready for the next step of development.
KerkoCite.ItemAlsoKnownAs: 10.1080/10400435.2015.1011758 10/f7svv7 2339240:PQ9MDIRA 2339240:S5PHSEX4 2405685:3JTWSRAR 2405685:V6F47JQW
Keywords: Visually Impaired Students (VIS); ___working_potential_duplicate; android platform; braille; education for VIS; mobile application

Efficacy of Think Tanks in Influencing Public Policies: The Case of Bangladesh - Rashid, A (Asian Journal of Political Science, 2013)
This article analyzes contextual and organizational challenges and constraints faced by think tanks in Bangladesh. It argues that while think tanks have been visible in the policy discourse through fostering policy debates and advocating policy proposals, their direct impact on policy outcomes remains limited. Think tanks’ research findings are often interpreted through the prism of politics. A number of think tanks are institutionally weak and face challenges in funding, attracting researchers, and retaining research focus. Think tanks can potentially focus attention to the wider policy community, and emphasize intermediate influences, such as, building capacity, wider networking and interacting with a broader base of policy-makers, in order to be effective and relevant in the policy discussions.
KerkoCite.ItemAlsoKnownAs: 10.1080/02185377.2013.793561 10/gkm64g 2339240:RD5SJH6B 2405685:C45YLVIG

Female Teachers' Perceptions of Quality Education for Adolescent Girls in Rural Bangladesh: A Case Study - Rahim, N (2017)
The education of adolescent girls in Bangladesh must be pursued with the right combination of technology, practicality, and cultural sensitivity to achieve, among other objectives, the objectives of Millennium Development Goals (MDGs). The problem this study address is despite the availability of mobile-based curricula, such as video, mobile phones, and Short Message System (SMS) technology, female teachers in rural areas are not trained to plan and deliver curricula using mobile platforms. The purpose of this qualitative single case study is to explore barriers associated with female teachers’ training of the use of mobile-based technology in rural areas in Bangladesh. The sample is, randomly selected a minimum of eight local female teachers who had been teaching at least for two years in a rural school in Bangladesh. The data were collected to determine the local teachers’ perception on establishing quality education through virtual (email, mobile phone, IMO, zoom or Skype) interviews administered to these 8 local female teachers. The researcher gathered data from the local female teachers’ point of view based on their motivation to receive training in becoming proficient in English and the use of mobile technology in teaching. A content analysis tool was used for analyzing, interpreting, coding, and categorizing textual data where themes identified based on a comprehensive classification system. The findings from the data analysis would aid schools in recruiting, training, and retaining local female teachers to provide quality education to the adolescent girls. The data from the single case study provided information as to the use of mobile and web technologies in teaching and learning while local female teachers gain proficiency in the English language. The insight gained from this single case study may help develop future technology budgets, infrastructure, and curriculum needs. The findings from research revealed that the rural Bangladeshi school teachers noted that there is limited use of videos in the classrooms for teaching due to, in some parts, the lack of training by school administrators on strategies to use videos in their teaching. Some barriers to the use of videos is due to the lack of Internet connection, the lack of knowledge on the proper use of videos in their teaching, and the lack of administrators’ support for this type of curriculum change in the schools.
KerkoCite.ItemAlsoKnownAs: 2339240:MKU6GYRJ 2405685:VDGJUDEZ

Mothers' and Fathers' Perceived Engagement in Children's Care and Schooling in Bangladesh: A Rural-Urban Comparison - Hossain, Ziarat; Atencio, David J. (Journal of Comparative Family Studies, 2017)
Couched within the bioecological systems theory, this paper examined whether (i) mothers and fathers differed in their perceived engagement with their school-age children's routine care, care on demand, academic interaction at home, and academic interaction at school; (ii) mothers' and fathers' engagement varied as a function of gender-of-child and rural and urban residence; and (iii) socioeconomic and support variables were associated with fathers' engagement with their children's care and academic work in twoparent rural and urban families in Bangladesh. Mother and father pairs from 40 rural and 41 urban families participated in the study. Mothers and fathers were separately interviewed to collect the data. Mothers spent more time in children's routine care and academic interaction at home than fathers did in both rural and urban families. Urban parents spent more time with their children than rural parents did. While rural mothers spent more time in sons' routine care and academic interaction at home than they did with daughters, urban fathers spent more time with sons' routine care than they did with their daughters. Whereas fathers' age and number of children negatively and length of marriage positively predicted fathers' engagement in children's routine care, fathers' age negatively and length of marriage and extra-familial support positively predicted fathers' engagement in children' academic interaction at home in rural families. Findings are discussed in relation to rural and urban fathers' changing roles in children's care and intellectual development in Bangladesh. Formulé dans la théorie des systèmes biologiques et écologiques, cet article examine dans quelle mesure (i) l'engagement des mères et des pères diffère dans les soins directs ou indirects donnés à leurs enfants d'âge scolaire, ainsi que dans leur suivi scolaire à domicile et à l'école; (ii) l'implication des mères et des pères varie en fonction du sexe de l'enfant et de son lieu de résidence rural ou urbain; et (iii) les variables socio-économiques et de soutien sont associées à la motivation des pères dans les soins et l'éducation de leurs enfants pour les familles biparentales rurales et urbaines au Bangladesh. La participation à cette étude comprend des couples mère-père provenant de 40 familles rurales et 41 familles urbaines. Les mères et les pères sont interrogés séparément pour la collecte de données. Les mères consacrent plus de temps que les pères aux soins directs des enfants et au suivi scolaire à domicile, aussi bien dans les familles rurales que les familles urbaines. Les parents en milieu urbain consacrent plus de temps à leurs enfants que les parents en milieu rural. Tandis que les mères en milieu rural consacrent plus de temps aux soins directs et suivi scolaire de leurs fils plutôt que de leurs filles, les pères en milieu urbain consacrent par ailleurs plus de temps que les mères aux soins directs de leurs fils. D'autre part, l'impact négatif de l'âge des pères et du nombre d'enfants ainsi que l'impact positif de la durée du mariage influent sur l'implication des pères dans les soins directs, tandis que l'impact négatif de l'âge des pères et l'impact positif de la durée du mariage et de la prise en charge extra-familiale présagent l'implication des pères dans le suivi scolaire des enfants à domicile chez les familles rurales. Les résultats sont examinés en rapport avec l'évolution du rôle des pères dans les soins et le développement intellectuel des enfants en milieu rural et urbain au Bangladesh. Basado en la teoría de los sistemas bioecológicos, este documento examinó si (i) las madres y los padres se diferenciaron de su participación percibida con el cuidado de rutina de sus hijos de edad escolar, el cuidado por encargo, la interacción académica en el hogar y la interacción académica en la escuela; (ii) la participación de las madres y los padres variaba en función de género de niño y de la residencia rural y urbana; y (iii) las variables socioeconómicas y las de apoyo se asociaron con la participación de los padres con el cuidado de sus hijos y su trabajo académico en las familias rurales y urbanas con dos padres en Bangladesh. Pares de un padre y una madre de 40 familias rurales y 41 urbanas participaron en el estudio. Las madres y los padres fueron entrevistados separadamente para recopilar la información. Las madres pasaban más tiempo con el cuidado de rutina de los niños y la interacción académica en el hogar que los padres en las familias rurales y urbanas. Los padres urbanos pasaban más tiempo con sus hijos que los padres rurales. Mientras que las madres rurales pasaban más tiempo en el cuidado de rutina y la interacción académica de sus hijos en casa que con sus hijas, los padres urbanos pasaban más tiempo con la atención de rutina de sus hijos que con sus hijas. Mientras que la edad del padre y el número de hijos negativamente predijeron la participación en la atención habitual de sus hijos y la duración del matrimonio predijo positivamente la participación del padre en la atención habitual de sus hijos, la edad del padre y la duración del matrimonio y el apoyo extrafamiliar predijeron positivamente la participación de los padres en la interacción académica de los niños de familias rurales. Los hallazgos se discuten en relación con los roles cambiantes de los padres rurales y los padres urbanos con el cuidado de sus hijos y el desarrollo intelectual de sus niños en Bangladesh.
Publisher: Dr. George Kurian KerkoCite.ItemAlsoKnownAs: 10.3138/jcfs.48.4.289 2339240:KBS8X3LS 2405685:V2DDIL9P

Bangladesh Tertiary Education Sector Review - Rahman, T; Nakata, S; Nagashima, Y; Rahman, M; Sharma, U; Rahman, M.A. (World Bank, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:WMUIJ9VC 2405685:VCP3HEWK

Parenting in context: Parents’ experiences of caring for a child with autism in Bangladesh - Uddin, Mohammad Jasim; Ashrafun, Laila (International Journal of Anthropology and Ethnology, 2023)
Although research on children with autism, their parents, and family-provider relations has substantially increased around the world, there has been a paucity of qualitative studies conducted on autism in developing countries or cross-cultural contexts. This qualitative study aims to explore parents’ experiences of raising a child with autism, as well as how autism is framed in everyday cultural contexts in Bangladesh. Using a semi-structured interview schedule, the study conducted interviews with four fathers and eighteen mothers of children with autism. The findings of this study reveal that parents who care for a child with autism experience emotions of sadness, frustration, and isolation. Despite the immense challenges that come with raising a child with autism, many parents report that their stress and anxiety are compounded by the stigma, avoidance, and disparaging remarks they receive from their own family members and neighbors. The findings of this study may help researchers and healthcare professionals understand better as to how local cultural beliefs, experiences, and understandings influence, how parents and families care for and view the development of their children with autism, and how they look for support and treatment services.
KerkoCite.ItemAlsoKnownAs: 10.1186/s41257-023-00089-w 2339240:FST7HD8T 2405685:IETYVWPW
Keywords: Autism; Bangladesh; Isolation; Parenting; Qualitative research; Stigma

Managing the Paradox of PublicPrivate University Funding: Bangladesh Context - Hossain, M; Hoque, M
KerkoCite.ItemAlsoKnownAs: 2339240:VXENFI2S 2405685:KXCCZ3EA

Pocket Book on Bangladesh Education Statistics 2017 - BANBEIS (Bangladesh Bureau of Education Information and Statistics, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:ZHXMREZX 2405685:7BICVCRT

Adolescence in the Time of Covid-19: Evidence from Bangladesh - Baird, Sarah; Seager, Jennifer; Sabarwal, Shwetlena; Guglielmi, Silvia; Sultan, Maheen (2020)
This note examines the effects of COVID-19 and subsequent economic and educational disruptions on adolescent well-being in Bangladesh. The analysis is based on data from 2,095 in-school adolescents aged 10–18 collected preCOVID-19 (February–March 2020) through a field survey for an ongoing impact evaluation, and a follow-up virtual survey undertaken early in the pandemic (May–June 2020). Findings show large household-level economic impacts associated with increased food insecurity, anxiety, and mental health issues among adolescents. In addition, school closures have decreased adolescents’ access to learning, increased time spent on household chores, and affected future job aspirations. The impacts are particularly large for girls and for adolescents from more vulnerable households. Policy makers need to consider policies that facilitate school return, targeting girls and the most vulnerable. They also need creative school-based programming to address the likely long-run physical and mental health effects of COVID-19 on young people.
KerkoCite.ItemAlsoKnownAs: 2339240:VBAB3NLH 2405685:4FAR45UM

Early effects of the COVID-19 lockdown on children in rural Bangladesh - Makino, Momoe; Shonchoy, Abu S; Wahhaj, Zaki (2021)
Using data collected through a telephone-based survey in rural Bangladesh during the height of the pandemic, we present evidence on the eﬀects of COVID-19-led lockdown and school closures on children, focusing on three child-related outcomes: time use of children during the school closure, plans regarding children’s schooling continuation, and the incidence of child marriages. Our analysis reveals heterogeneity in the eﬀects of lockdown and school closure in terms of the child’s gender and the type of shocks. We ﬁnd a decrease in children’s study time and an increase in time spent on household chores during the school closure, and these changes were signiﬁcantly larger for girls than for boys. Within the household, respiratory illness lowered expectations that a child would return to school and increased the probability of marriage-related discussions for girls. Our ﬁndings oﬀer a cautionary tale regarding the potential longterm eﬀects of pandemic for girls in developing countries.
KerkoCite.ItemAlsoKnownAs: 2339240:EHS3BXYL 2405685:HBIVSCZT
Keywords: ⛔ No DOI found

Access and equity in Open Education Resources: E-learning for girl and women in Bangladesh Open University. - Billah, Masum (2013)
Open Educational Resources are freely accessible, usually openly licensed documents and media that are useful for teaching, learning, educational, assessment and research purposes. E-learning is (website, e-book, cd, DVD etc) latest addition to OER which is accessible through internet and computing systems. Though these resources are ‘open’ to all for learning, but the socio economic situation of women and girls in Bangladesh is a challenge to take the advantage of e-learning systems. This research has been carried out to comprehend the situation of women and girls in Bangladesh in terms of E-learning, identify the challenges and opportunities of access to E-learning among women and girls and recommend about further improvement of those systems. The research had been consisted of several stages of analysis. Primarily different e-learning systems have been identified and later the contents have been analyzed to explore whether the topics and knowledge are relevant to women and girls. In the next stage, two groups of girls have been selected as respondent groups among which one group has been selected as user group who are currently using e-learning systems, and other group has non-users group. Comparison between these two groups has helped to identify the challenges that some girls face to use e-learning system and to recognize the factors that facilitated some girls to use the elearning system. In further stage of analysis, information from user’s group has helped to explore about the contents that should be included in the e-learning systems especially for women education, which will ensure a gender balance to use the system. At the end, it is expected that the research can recommend two factors; firstly, how these e-learning system could be more accessible among girls/women through increasing knowledge about the systems, and; secondly, what is required to include in these system to ensure equity to use the system and to gain knowledge from it.
KerkoCite.ItemAlsoKnownAs: 2339240:QQ62CXHP 2405685:IREWUQKV
Keywords: ⛔ No DOI found

School-based teachers' professional development through technology-enhanced learning in Bangladesh - Mahruf C Shohel, M; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers' teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers' professional development. Using the case of a pre-pilot intervention in the Underprivileged Children's Educational Programs schools, it explores the teachers' professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers' professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Place: Abingdon Publisher: Taylor & Francis Ltd. shortDOI: 10/gf5f6p KerkoCite.ItemAlsoKnownAs: 10.1080/13664530.2012.668103 10/gf5f6p 2405685:NA7NT9BB 2534378:EYTQ9C76
Keywords: Bangladesh; Education–Teaching Methods And Curriculum; Educational technology; Learning; Professional development; Teacher education; UCEP-Bangladesh; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; technology-enhanced learning

Barriers to the Introduction of ICT into Education in Developing Countries: The Example of Bangladesh - Khan, Md. Shahadat; Hasan, Mahbub; Clement, Che (International Journal of Instruction, 2012)
Within a very few years, Information and Communication Technology (ICT) has turned out to be an effective educational technology which promotes some dramatic changes in teaching and learning processes. Technologies allow students to work more productively than in the past, but the teacher’s role in technology rich classrooms is more demanding than ever (Keengwe, Onchwari et al. 2008). ICT has the potential to transform the nature of education (improving teachers’ design work, enhancing the roles of students and teachers in the learning process and helping to create a collaborative learning environment, etc). Although ICT has the potential to improve the educational system to a great extent, developing countries are far from reaping these benefits because of certain barriers. The aim of this paper is to present a comprehensive review of international articles relating to barriers encountered when introducing ICT into classrooms. This review will help identify the factors that influence teachers’ decisions whether or not to implement ICT in teaching-learning situations. Connections will be made with existing literature to explore possible barriers for introducing ICT into education in Bangladesh. Further, this paper also offers a number of recommendations to reduce these barriers and maximize the beneficial use of ICT on education.
KerkoCite.ItemAlsoKnownAs: 2339240:ZVEEYPXK 2405685:ETUG4APG 2405685:NLFPM6QW
Keywords: ⛔ No DOI found

School-based teachers’ professional development through technology-enhanced learning in Bangladesh - Shohel, M. Mahruf C.; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers’ teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers’ professional development. Using the case of a pre-pilot intervention in the Underprivileged Children’s Educational Programs schools, it explores the teachers’ professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers’ professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Publisher: Routledge _eprint: https://doi.org/10.1080/13664530.2012.668103 KerkoCite.ItemAlsoKnownAs: 10.1080/13664530.2012.668103 10/gf5f6p 2339240:QYT78QZJ 2405685:AJFFY6AZ 2534378:EYTQ9C76 2534378:ILM8S5MC 2534378:L6R23M7S 2534378:PXRSVU2M 2534378:TBRE94GM 2534378:U2JMZZFP
Keywords: AUDIOVISUAL education; BANGLADESH; Bangladesh; COMPUTER assisted instruction; ENGLISH language – Study & teaching – Foreign speakers; Education–Teaching Methods And Curriculum; Educational technology; LANGUAGE teachers; Learning; PROFESSIONAL education; Professional development; SECONDARY school teachers; TEACHER development; TEACHERS – Attitudes; Teacher education; UCEP-Bangladesh; __:import:01; __:match:final; __:matched; __:study_id:2099954; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; teachers’ professional development; technology-enhanced learning

COVID-19 Response and Recovery Plan - Government of Bangladesh (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:LEYGY974 2405685:6W2B7V7U

Understanding the Digital Gender Divide in Rural Bangladesh: How wide it is and why - Zahan, Iffat (https://bigd.bracu.ac.bd/publications/understanding-the-digital-gender-divide-in-rural-bangladesh-how-wide-it-is-and-why/, 2021)
The digital gender divide (DGD) has become a major concern for policymakers. Globally, more men (58 per cent) use the internet than women (48 per cent). This gap can mainly be attributed to the gender gap in developing countries where...
KerkoCite.ItemAlsoKnownAs: 2339240:3687JNVS 2405685:P35H739H 2405685:TPUKZGVR

English in Action: a new approach to continuing professional development through the use of mediated video, peer support and low-cost mobilephones in Bangladesh - Woodward, Clare; Griffiths, Malcolm; Solly, Mike (Innovations In The Continuing Professional Development Of English Language Teachers, 2014)
KerkoCite.ItemAlsoKnownAs: 2405685:VLPHGQ5H
Keywords: C:Bangladesh

Making Vision 2041 a Reality: Perspective plan of Bangladesh 2021-2041 - Ministry of Planning (Ministry of Planning,Government of the People’s Republic of Bangladesh, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PCSGGS87 2405685:T9BWKY5Z

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651981 previousDOI: 10.5281/zenodo.5109678 previousDOI: 10.5281/zenodo.4943272 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4943272 10.5281/zenodo.5109678 10.5281/zenodo.5651981 2339240:TCHKGQZS 2405685:QUJHNPRD 2405685:XH44AG5R 2405685:YULPZE4D
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Baseline-Endline Report: Reaching the Unreached (RtU) through Open and Distance Learning (ODL) in Bangladesh, India and Pakistan - Ferreira, Frances; Cruz, Charisse; Smith, Kristina; Commonwealth of Learning (COL) (British Columbia) (Commonwealth of Learning, 2018)
This report documents the baseline-endline study by the GIRLS Inspire team's Reaching the Unreached project to examine the implications of skills training and education for women's and girls' empowerment and sustainable livelihoods in Bangladesh, India and Pakistan. It is based on data collected from quarterly reports mirrored against the project outcomes, meeting reports and surveys from March 2016 to March 2017. The quarterly and meeting reports documented the activities undertaken to provide training for unreached women and girls in the selected countries. While the actual training was offered exclusively to women and girls, the reports and surveys also captured the input of men and boys in terms of their participation in various community events and as staff members of the partner organisations.
KerkoCite.ItemAlsoKnownAs: 2339240:6XL37978 2405685:NM8GPWDQ
Keywords: Access to Education; Bangladesh; Barriers; Child Abuse; Decision Making; Distance Education; Dropouts; Economic Factors; Educational Attainment; Elementary Secondary Education; Employer Attitudes; Employment; Empowerment; Females; Foreign Countries; Health; Income; India; Job Skills; Marriage; Occupational Aspiration; Pakistan; Postsecondary Education; Program Effectiveness; Skill Development; Sustainability; Training; Womens Education

Bangladesh Engaging the Private Sector in Education: SABER Country Report 2016 - World Bank Group (World Bank, 2016)
KerkoCite.ItemAlsoKnownAs: 10.1596/26524 2339240:YEQL3HEG 2405685:8L2579LA

A simulation of COVID-19 school closure impact on student learning in Bangladesh - Rahman, Tashmina; Sharma, Uttam; World Bank (World Bank, 2021)
This Note presents results from a series of simulations that aim to capture the impacts that school closures in Bangladesh might have on the learning levels, enrollment and future earnings of children and students using a methodological tool developed by the Education Global Practice of the World Bank. We find that overall loss in learning for every child enrolled in school even in the most optimistic scenario is expected to be substantial and the economic implications of the learning losses are huge. Available data also indicates that remote learning requires to be made more effective. It is hoped that the insights from this note will be useful for the government, non-government, private sector and civil society engaged in education service delivery as they are attempting to forge effective partnerships during and after the crisis. There is an urgent need to substantially reduce additional dropouts and absenteeism through stipends and safe school opening and communication campaigns.
KerkoCite.ItemAlsoKnownAs: 2339240:WGZJQAIX 2405685:BS37TZAZ
Keywords: Access to Computers; Access to Education; Achievement Gains; Age Differences; At Risk Students; Attendance; Bangladesh; Barriers; COVID-19; Delivery Systems; Disadvantaged Youth; Distance Education; Dropout Prevention; Economic Impact; Elementary Secondary Education; Foreign Countries; Gender Differences; Handheld Devices; Income; Pandemics; Partnerships in Education; Program Effectiveness; Radio; Remedial Instruction; Rural Urban Differences; School Closing; Simulation; Telecommunications; Television

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5721401 10.53832/edtechhub.0070 2339240:CHJR9D5G 2339240:RFJZSHMG 2405685:FE3VBQQW 2405685:NFXKD34I 2405685:PU8D6GXN 2405685:SY9TIAMH
Keywords: _r:AddedByZotZen

Impact of COVID-19 on the institutional education system and its associated students in Bangladesh - Emon, Efta Khairul Haque; Alif, Ashrafur Rahman; Islam, M. Shahanul (Asian Journal of Education and Social Studies, 2020)
KerkoCite.ItemAlsoKnownAs: 10.9734/ajess/2020/v11i230288 2339240:X4UBFSR8 2405685:P48U5KA8
Keywords: Bangladesh; COVID-19; Coronavirus; education; impact; poverty.

Possibilities of using Mobile Technology to improve Early Grade Reading in Bangladesh: Towards a Practical Framework - Ahsan, Sumera; Hossain, Md; Sarwar, Sheikh (2019)
Using mobile phones can enhance literacy skills such as reading. However, the success in terms of gain in reading skill using mobile phones depends on manifold conditions and factors which are context dependent. Therefore, the process of implementation of initiative that used mobile phones for boosting literacy is worth exploring in different contexts. The aim of this research project was to capture the first impression of the stakeholders related to the mBoost project, a project that used voices and text to help teachers and parents use activities to enhance children's reading skills, immediately after its piloting. Data was collected through qualitative interview, observation, and FGDs with parents, teachers, students, and relevant Save the Children Staff. This research found that three types of factors, technical, socio-cultural, and individual end user characteristics affected the implementation process in four phases (sending, receiving, comprehending, and implementing text and voice message activities) narrowing down the targeted benefits.
KerkoCite.ItemAlsoKnownAs: 2339240:5YUYY2RL 2405685:KSGSB638

Focus country: Bangladesh - EdTech Hub (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:R62Y25DW 2405685:IFIR3QC9

Bangladesh Education Sector Analysis - GPE (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PU356S5T 2405685:C7TES4HM

Population, total - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:HXP4NC9X 2405685:FY2PMI2Y

Population growth (annual %) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:56YJRP9F 2405685:GTPKXNXJ

Secondary education, pupils - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KTBRX27R 2405685:F2U9JVYV

Secondary education, teachers - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:UDK7XP58 2405685:EKHHRCF2

Scaling Online Teacher Professional Development in Bangladesh: Bangladeshi teachers’ experiences of the online training for the National Curriculum Revision - Afzal, Nimra; Atuly, Afsana Sadiq; Mazari, Haani; Clark-Wilson, Alison (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15005589 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1102 ZenodoArchiveConcept: 15005588
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Education For All national review: Bangladesh - UNESCO (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:Y6BD7X9X 2405685:MGHEJJ7F

School enrollment, secondary (% net) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2E6RZ789 2405685:V7GDFZV7

Secondary education, pupils (% female) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KPLXFGAC 2405685:LDBMGJIF

Secondary education, teachers, female - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:EB4PD5EG 2405685:LB4ZKJHT

Is civil society in trouble in Bangladesh? - Lewis, D (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:ESCEXEUH 2405685:IJQ2EZ6Y

Rural population (% of total population) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VDAAYFPJ 2405685:3K9WFJ7B

Bangladesh - COVID 19 School Sector Response Project (English) - World Bank (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:KGIQQEBE 2405685:IKNKMG2R

How civil society influences education policy in Bangladesh - Hoque, E (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:VK5AVDHJ 2405685:5RZ7G7TC

The Potential of Mobile Phones to Transform Teacher Professional Development to Build Sustainable Educational Futures in Bangladesh - Walsh, Christopher S; Woodward, Clare; Solly, Mike; Shrestha, Prithvi (Asian Association of Open Universities Journal, 2015)
Futures thinking is used by governments to consider long-term strategic approaches and develop policies and practices that are potentially resilient to future uncertainty. English in Action (EIA), arguably the world's largest English language teacher professional development (TPD) project, used futures thinking to author possible, probable and preferable future scenarios to solve the project's greatest technological challenge: how to deliver audio-visual TPD materials and hundreds of classroom audio resources to 75,000 teachers by 2017. Authoring future scenarios and engaging in possibility thinking (PT) provided us with a taxonomy of question-posing and question-responding that assisted the project team in being creative. This process informed the successful pilot testing of a mobile-phone-based technology kit to deliver TPD resources within an open distance learning (ODL) platform. Taking the risk and having the foresight to trial mobile phones in remote rural areas with teachers and students led to unforeseen innovation. As a result, EIA is currently using a mobile-phone-based technology kit with 12,500 teachers to improve the English language proficiency of 700,000 students. As the project scales up in its third and final phase, we are using the new technology kit — known as the 'trainer in your pocket' — to foster a 'quiet revolution' in the provision of professional development for teachers at scale to an additional 67,500 teachers and nearly 10 million students.
Publisher: Emerald Group Publishing Limited shortDOI: 10/ggx3rj KerkoCite.ItemAlsoKnownAs: 10.1108/AAOUJ-10-01-2015-B005 10/ggx3rj 2405685:6AFZ29KK

World Bank helps Bangladesh provide education and skills training to poor children and youths - ReliefWeb (OCHA, 2021)
English News and Press Release on Bangladesh about Contributions, Education, Epidemic and more; published on 18 Jan 2021 by World Bank
KerkoCite.ItemAlsoKnownAs: 2339240:YW8V8Z46 2405685:BLFQEDDB

Building a globalised research system – the case of Bangladesh - Irfanullah, H (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:FYJUZ95H 2405685:CJIZGFZR

COVID-19 boosts digitization of higher education in Bangladesh - Rahman, M; ul-Aziz, M; Ahmed, S (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:YMV5DY38 2405685:F66HV332

Population ages 15-64 (% of total population) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7R2JJF4R 2405685:5NXMIQQ7

C-DELTA: Preparing students as digital leaders in Bangladesh - Khan, S (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:395TDINJ 2405685:SUZI34L7
Keywords: ⛔ No DOI found

Keeping Bangladesh’s Students Learning During the COVID-19 Pandemic - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ARRPM4JP 2405685:B9E9UBBB

Bangladesh: Using open school data to improve transparency and accountability - Roy, Dipu; Miah, Abu Said Juel (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:4NX242AQ 2405685:N27R4JLA
Keywords: ⛔ No DOI found

Coronavirus Outbreak, Schooling and Learning: Study on Secondary School Students in Bangladesh - Asadullah, N; Bhattacharjee, A; Tasnim, M; Mumtahena, F (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Q68A9V5S 2405685:KEVNB97X

Education sector plan (ESP) for Bangladesh: Fiscal years 2020/21-2024/25 - MoE (Ministry of Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:QEU82LB4 2405685:6AMSJQTC

Increasing Interactivity in Distance Educations: Case Studies Bangladesh and Sri Lanka - Andersson, Annika; Hatakka, Mathias (Information Technology for Development, 2010)
KerkoCite.ItemAlsoKnownAs: 10/fwqgg2 2339240:E6E7FILP 2405685:3HQDVULN

Mental health and learning: BRAC’s response in Bangladesh during Covid-19 - Ahmad, J; Mariam, E; Sadaf, B; Sarwar, S; Siddique, S; Zaman, S (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:NT98ND5A 2405685:S58SFAFK

A gender digital divide? Women learning English through ICTs in Bangladesh - Tyers, A (CEUR Workshop Proceedings. 955. 94-100., 2012)
KerkoCite.ItemAlsoKnownAs: 2339240:YQWH7XU4 2405685:6YTLB5YY
Keywords: ⛔ No DOI found

Localization of Digital Content for Use in Secondary Schools of Bangladesh - Chowdhury, M. D.; Al-Mahmood, A; Bashar, M. A.; Ahmed, J. U. (2011)
KerkoCite.ItemAlsoKnownAs: 2339240:XLFK5MLF 2405685:ZHXAJX88
Keywords: ⛔ No DOI found

Summative Evaluation of GPE’s Country-Level Support to Education: Bangladesh - GPE (Global Partnership for Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:VBSUZLDH 2405685:EHB63PAS

Teacher educators’ perspectives of the introduction of ICT in education in Bangladesh - Chowdhury, M (Critical Literacy: Theories and Practices, 2012)
KerkoCite.ItemAlsoKnownAs: 2339240:INLPU2EQ 2405685:72TSTWR5
Keywords: ⛔ No DOI found

WFP and Government of Bangladesh deliver high-energy biscuits to school children affected by COVID-19 school closures - WFP (ReliefWeb, 2020)
English News and Press Release on Bangladesh about Education, Food and Nutrition and Epidemic; published on 19 May 2020 by WFP
KerkoCite.ItemAlsoKnownAs: 2339240:HZUY9LBT 2405685:9Z9XFPC8

An Evaluation of Computer Aided Learning (BRAC-CAL) in Secondary Schools in Bangladesh. - Power, T; Babu, R; Chowdhury, T (BRAC Research and Evaluation Division, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:HY6ESF47 2405685:7BA7PQLP

Human Development Report 2020: The Next Frontier - Human Development and the Anthropocene. Bangladesh. - United Nations Development Programme (United Nations, 2020)
KerkoCite.ItemAlsoKnownAs: 10.18356/9789210055161 2339240:ZBYSBI9Y 2405685:225TWATP
Keywords: ___working_potential_duplicate

Skills-Building Programs to Reduce Child Marriage in Bangladesh: A Randomized Controlled Trial - Amin, S; Saha, J; Ahmed, J (Journal of Adolescent Health Volume 63, Issue 3, September 2018, Pages 293-300, 2018)
KerkoCite.ItemAlsoKnownAs: 10/gd96mw 2339240:KQXGLUE6 2405685:39W3RT7X

Assessment of Distance Learning Initiative of the Government of Bangladesh during COVID-19 Pandemic - Das, H (a2i, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:QP4P29MJ 2405685:BV6K34UF

Master plan for ICT in education in Bangladesh (2012-2021): Progress Review Report 2019 - MoE (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:JAJI53M3 2405685:QPP65VTW

ICT Using Situation in Rural and Urban Primary Schools of Bangladesh: A Comparative Study - Ali, M (Prime University Journal, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:E6NMCEBE 2405685:XHR99KDS
Keywords: ⛔ No DOI found

Take-up, Use, and Effectiveness of Remote Learning Technologies in Bangladesh during COVID-19 - Beam, E; Mukherjee, P; Navarro-Sola, L (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2BEQ3IEH 2405685:PW8FDPUE

How BRAC is supporting Bangladesh to continue education in a pandemic - Chowdhury, Zaian; Islam, Rubab; Saltmarsh, Sarah-Jane (2020)
Library Catalog: blog.brac.net Section: Learning KerkoCite.ItemAlsoKnownAs: 2339240:62DZHUDL 2339240:YPXY5VS5 2405685:8CMZMYMX 2405685:JGHI5FAV
Keywords: ___working_potential_duplicate

Innovative Delivery of Education in Bangladesh Using Mobile Technology - Cristol, Dean; Al-Sabbagh, Samah; Abdulbaki, Anwar; Majareh, Maryam; Tuhin, Salah Uddin; Gimbert, Belinda (2019)
Given the increasing use and accessibility of mobile technology, a pilot study, “Innovative Delivery of Education in Bangladesh Using Mobile Technology” was carried out using mobile learning devices to both increase and enrich the delivery of educational services in a remote Bangladesh district. The APTUS system was used to allow learners’ connection to digital learning platforms and content without electricity or internet access. The researchers maintained that mobile learning associated with Project Based Learning can effect student learning in five ways: (1) contingent learning, changing...
KerkoCite.ItemAlsoKnownAs: 2339240:4FSQZLHQ 2405685:2CUIABK2

Bangladesh Primary Education Annual Sector Performance Report 2019 - Directorate of Primary Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:YZZV53KC 2405685:BZR78EKI

Reaching the Unreached (RtU) through Open and Distance Learning (ODL) in Bangladesh, India and Pakistan - Ferreira, F; Cruz, C; Smith, K (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:ISYEPM5P 2405685:W55NCH9D

Conditional Cash Transfer, Loss Framing, and SMS Nudges: Evidence from a Randomized Field Experiment in Bangladesh - Fujii, Tomoki; Ho, Christine; Ray, Rohan; Shonchoy, Abu (2021)
Conditional cash transfers (CCTs) have become one of the most common policy interventions to increase school attendance, but the cost-eﬀectiveness of such interventions has not attracted the attention it deserves. Hence, in addition to a standard CCT implementation, we experimentally study two potential ways to improve the cost-eﬀectiveness of school attendance interventions: (i) SMS information nudges and (ii) loss framing in CCTs. The former provides school attendance information to parents and the latter exploits the endowment eﬀect. Consistent with the existing literature, CCT intervention signiﬁcantly increases school attendance. We also ﬁnd that the loss framing marginally increases attendance over and above the ∗We would like to thank Joseph Altonji, James Berry, Barbara Biasi, Gaurav Dutt, Maulik Jagnani, Costas Meghir, Rohini Pande, Rebecca Thornton, and seminar attendees at Monash and Yale for insightful comments and suggestions. We also thank Akshat Daga, Alekhyo Roychowdhury, Ishaan Malik, and Snehal Modi for research assistance. We beneﬁted from data collection support from MOMODa Foundation and technical support from the Metakave team to automate the process of sending SMS. Finally, we express our sincere gratitude to the participating schools, the students, their parents, and the teachers. Funding from the Shirin Fozdar and Singapore Ministry of Education Academic Research Fund Tier 1 Grant (17-C244-SMU-004) and Japan Center for Economic Research are gratefully acknowledged. This research was approved by the Singapore Management University Institutional Review Board (IRB-16-082-A092-C2(220)). The trial in this study was registered in the AEA RCT registry under AEARCTR-0002373. All mistakes remain ours.
KerkoCite.ItemAlsoKnownAs: 2339240:KUH42MFY 2405685:JG23VUNM
Keywords: ⛔ No DOI found

A Simulation of COVID-19 School Closure Impact on Student Learning in Bangladesh [Book Chapter] - Rahman, Tashmina; Sharma, Uttam (World Bank, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1596/35043 2339240:4MHUSRIF 2405685:RDF4ZFYM

Staying Tuned Radio Programming for Sustained Behaviour Change and Accountability in Cox’s Bazar, Bangladesh - Ergül, H (UNICEF, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:GJPSTJEE 2405685:DUQRTVUY

The Effectiveness of Using Technology in English Language Classrooms in Government Primary Schools in Bangladesh - Parvin, Ruxana Hossain; Salam, Shaikh Flint (FIRE: Forum for International Research in Education, 2015)
Across the globe, governments of different countries have recognized the importance and value of digital technologies in language learning. This article is based on the pilot project of Save the Children using information and communication technology (ICT) in education. Through this initiative, interactive multimedia software based on national curriculum of English Class 4 were developed and tested in selected government primary schools. The pre-intervention survey indicated that the teachers do not have the language competence to confidently facilitate English classes using the Communicative Language Teaching (CLT) approach. The results of the project showed that the use of audio-visual content has strong potential for enhancing and promoting interactive language classes. However, the success of the program depends on how the technology is designed and implemented and how the teachers are trained to use it.
KerkoCite.ItemAlsoKnownAs: 10/gkm64q 2339240:5MMI3MEV 2405685:B5DM3N9I

Teacher professional development using mobile technologies in a large-scale project: lessons learned from Bangladesh - Shrestha, Prithvi (International Journal of Computer-Assisted Language Learning and Teaching (IJCALLT), 2012)
Publisher: IGI Global KerkoCite.ItemAlsoKnownAs: 10.4018/ijcallt.2012100103 10/gftr3z 2339240:6D45UDBE 2405685:SU6CDMZY 2534378:KGBGU7A7 2534378:LQMP437N

Population ages 0-14 (% of total population) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QGQ9PZAD 2339240:R4T4RZYH 2405685:6VPIRD86 2405685:BS9S34JU

Bangladesh Education Sector Public Expenditure Review - Bhatta, Saurav Dev; Genoni, Maria Eugenia; Sharma, Uttam; Khaltarkhuu, Buyant Erdene; Maratou-Kolias, Laura; Asaduzzaman, T. M. (World Bank, 2019)
Adequate investment in human capital development is critical for enabling Bangladesh to reach its goal of becoming an upper middle-income country. Bangladesh, currently a lower-middle country with an annual per capita gross national income (GNI) of USD 1,470 (WDI 2019), aims to attain upper-middle income status by 2021 and eliminate poverty by 2030. Recognizing the importance of investing in education for building its human capital base, the government of Bangladesh (GoB) has been allocating a large portion of the national budget to the education sector each year during the past two decades. Effective utilization and equitable distribution of allocated public spending is important for ensuring adequate progress in education outcomes. This report analyzes major spending and outcomes trends in the overall education sector in recent years, with a focus on primary and secondary education. Responding to the recommendation of the 2015 Bangladesh Public Expenditure Review Update for more analytical work on public spending in different sectors, including education, the current study analyzes the trends in major education expenditures, access to education, quality of education, and disparities in education outcomes in the past two decades. It also looks at the composition of education expenditure, consistency between budget allocations and actual expenditures, equity in education spending, and potential links between spending and key educational outcomes. Because of data limitations, this report focuses mainly on primary and secondary education. It is expected that this analysis will add to the literature on investments in the Bangladesh education sector and inform discussions on identifying policy priorities and making resource allocation decisions in the sector.
Accepted: 2021-07-19T16:19:39Z KerkoCite.ItemAlsoKnownAs: 2339240:W64P6523 2405685:HJVFISKT 4656463:CYJBRSJM
Keywords: Education Budget; Education Expenditure; Education Outcomes; Equity in Education; Public Expenditure Review

Final Report on: Assessment of Distance Learning Initiative of the Government of Bangladesh during COVID-19 Pandemic - a2i (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Q6R8864R 2405685:3K8CG3MF

Combatting the impact of COVID-19 school closures in Bangladesh - Rahman, Tashmina; Ahmed, Ramim (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:N456FTY7 2405685:27LNFHVR

The effect of using Teams Games Tournaments (TGT) cooperative technique for learning mathematics in secondary schools of Bangladesh - Salam, Abdus; Hossain, Anwar; Rahman, Shahidur (Journal of Research in Mathematics Education, 2015)
shortDOI: 10/ggjhr6 KerkoCite.ItemAlsoKnownAs: 10.17583/redimat.2015.1519 10/ggjhr6 2339240:IT93WMC2 2405685:G7CDSHGB

A Rapid Assessment: Impact of COVID-19 on Education in Bangladesh - BRAC (Advocacy for Social Change (ASC), BRAC, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:8UGKK4SX 2405685:7PRVRPXW

Summative Evaluation of GPE's Country-level Support to Education. Bangladesh - Results for Development (Universalia, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:2UZNK2DF 2405685:JCNQQAWC

Delaying child marriage through community-based skills-development programs for girls: Results from a randomized controlled study in rural Bangladesh - Amin, Sajeda; Ahmed, Johana; Saha, Jyotirmoy; Hossain, Md.; Haque, Eashita (Population Council, 2016)
KerkoCite.ItemAlsoKnownAs: 10.31899/pgy9.1009 2339240:YW7SLW72 2405685:QGJZ86U6

The Teachers’ Portal as a tool for teachers’ professional development in Bangladesh: Facilitating nationwide networking and digital multimedia content for 40,000 schools - Hansson, H; Sultana, S; Sarwar, A; Ahmed, F; Uddin, R; Saha, P; Islam, G; Islam, M (International Journal of Education and Development using ICT, 2018)
The Teachers’ Portal (teachers.gov.bd) is an online platform for Bangladeshi teachers designed to store and retrieve digital educational contents of different subjects useful for classroom teaching and students’ learning. The portal also facilitates professional networking among teachers across the country. This study aims to find out the benefits of using this Portal and associated challenges from teachers’ perspective. Following a mixed methods research approach Teachers, head teachers, teacher educators from primary, secondary, madrasa and vocational educational institutions and specialists on teachers’ Portal (N=410) were interviewed and consulted for the study. Telephone interviews, online surveys, Key Informant Interviews (KII), Focused Group Discussions (FGD), Face-to-Face interviews, and large consultative workshops were used to collect data. The results suggest that teachers are motivated to use the Portal as its contents stimulate students’ creativity and encourage students’ active participation in classrooms learning. Besides, it empowers teachers in a number of ways. However, internet connectivity, slow Internet speed, power failure, technical issues, high cost of Internet and unavailability of equipment are found as major challenges. In short, the Teachers’ Portal is a key driver for changing Bangladeshi education and preparing the young generation with quality education.
KerkoCite.ItemAlsoKnownAs: 2339240:YUIF5MMJ 2405685:ZSXBG9LT
Keywords: ⛔ No DOI found

The Politics of Learning Reforms in Bangladesh Naomi , Mirza M. Hassan, Muhammad Ashikur Rahman, Khondoker Shakhawat Ali, and Md. Sajidul Islam Introduction - Hossain, N; Hassan, M; Rahman, M; Ali, K; Islam, Md (The politics of education in developing countries: from schooling to learning, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:4KSRXN8F 2405685:APF6QN7D
Keywords: Developing countries; Education; Education and state; Political aspects

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
shortDOI: 10/gftr32 KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2013.766232 10/gftr32 2405685:WABHFRL5
Keywords: ___working_potential_duplicate

English Language Classroom Practices: Bangladeshi Primary School Children’s Perceptions - Shrestha, P (RELC Journal, 2013)
English language teaching (ELT) has been investigated from various angles including how English language teachers perceive what happens in an ELT classroom. How primary school English language learners perceive their experiences of ELT is rarely reported in the published literature, particularly from developing countries such as Bangladesh. This article reports on a study that examined Bangladeshi primary school learners’ experience of English language classroom practices in which technology-enhanced communicative language teaching activities were promoted through a project called English in Action (EIA). EIA is a large-scale 9-year long international English language development project in Bangladesh, funded by the UK government. A semi-structured group interview was conducted with 600 Grade 3 students from different regions of Bangladesh. The findings showed that the learners found communicative language learning activities such as dialogue and role play more effective than translation and memorizing grammar rules for learning English, although they enjoyed reciting and drills. The results also showed that these learners’ English teachers tended to mix both traditional and communicative approaches in their lessons. The paper critiques EIA and argues that any major language development project needs to consider the local context and learners’ views on language learning for its success.
KerkoCite.ItemAlsoKnownAs: 10.1177/0033688213488466 10/gkm64m 2339240:LWI8RXJE 2405685:2V2WHBZB

Sisimpur’s reach and educational impact: Evidence from a national longitudinal survey of a Sesame Street project in Bangladesh. - Lee, H.J. (Sesame Workshop, 2009)
KerkoCite.ItemAlsoKnownAs: 2339240:KIX4GIDD 2405685:JU9AZWT2 4803016:35JDVYDE

Sesame street in the tea estates: A multi-media intervention to improve sanitation and hygiene among Bangladesh's most vulnerable youth - Borzekowski, Dina (Annals of Global Health, 2015)
shortDOI: 10/gg26fp KerkoCite.ItemAlsoKnownAs: 10.1016/j.aogh.2015.02.748 10/gg26fp 2339240:8Q2HKU7I 2405685:8RY3PYAF 4803016:Y5CF7KER

Summary: Webinar on COVID-19 fallout on poverty and livelihoods in Bangladesh: results from SANEM’s nation-wide survey conducted in Nov-Dec 2020 - SANEM (SANEM, 2021)
The 10th episode of SANEM Shongzog on "COVID-19 Fallout on Poverty and Livelihoods in Bangladesh: Results from SANEM's Nationwide Survey (Nov-Dec 2020)" was held on 23 January 2021.
KerkoCite.ItemAlsoKnownAs: 2339240:KE7K5Y72 2405685:9MSRWZEF

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
shortDOI: 10/gftr32 KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2013.766232 10/gftr32 2405685:WABHFRL5
Keywords: ___working_potential_duplicate

AI governance in Bangladesh: A critical evaluation of the transition from strategic vision to policy framework - Karmakar, Abir (Indian Journal of Legal Review, 2024)
This article critically evaluates the progression of Bangladesh’s Artificial Intelligence (AI) governance, focusing on the transition from the National AI Strategy 2020 to the Draft AI Policy 2024. The 2020 Strategy set the foundation for AI-driven national development, though it lacked specific implementation mechanisms. The Draft AI Policy 2024, however, introduces more concrete frameworks centered on regulation, ethics, data governance, and capacity building. By comparing these policy documents, the article highlights Bangladesh’s efforts to balance innovation with responsibility, addressing challenges such as ethical AI use, data privacy, and workforce development. This analysis reflects the country’s commitment to aligning AI governance with global standards while fostering sustainable and inclusive AI adoption.
KerkoCite.ItemAlsoKnownAs: 2339240:X3L9W5XC 2405685:K8BDAGJZ
Keywords: ⛔ No DOI found

Reaching the Unreached through Open and Distance Learning (ODL) in Bangladesh, India and Pakistan - Ferreira, F (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:ZDU284P6 2405685:QZQE2876
Keywords: ___working_potential_duplicate

A rapid assessment: Impact of COVID-19 on Education in Bangladesh - Advocacy for Social Change, BRAC; BRAC Education Programme (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:JEFXQAWR 2405685:B2L94Z4W

A Simulation of COVID-19 School Closure Impact on Student Learning in Bangladesh [Web page] - Rahman, Tashmina; Sharma, Uttam (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KMHYAN74 2405685:5NGZFQW4

HELLO: An Android-based mobile application for autism individuals to improve socio-communicational learnability in Bangladesh - Jahan Yra, Ishrat; Hossain Pranto, Maksud; Das, Amit Kumar (2022 16th International Conference on Ubiquitous Information Management and Communication (IMCOM), 2022)
Autism Spectrum Disorder (ASD) individuals experience many troubles in communication and lag in social improvement. In this significant circumstance, the appearance of smart technologies has kept promising success regarding Autism Spectrum Disorder (ASD). Many socio-developmental mobile applications have been created in developed countries. In contrast, there are no such applications in developing countries like Bangladesh in native content. In this paper, an Android-based mobile application named HELLO is designed with the fundamental thought of Picture Exchange Communication System (PECS) in the Bangla language. This application aims to improve the socio-communicational learnability of autism individuals in Bangladesh. It is expected that our application can be brilliant support to autism individuals, also included the people who endure non-verbal inconveniences. The outcome of this application demonstrates a positive streamline to the improvement in communicating with others.
KerkoCite.ItemAlsoKnownAs: 10.1109/IMCOM53663.2022.9721813 2339240:X5TY4Z3B 2405685:BAETJBXJ
Keywords: ASD; Autism; Autism Individuals; Bangla language; Communication systems; Developing countries; HELLO; Information management; Mobile Application; Mobile applications; PECS; Propulsion; Smart Technologies; Socio-Communicational; Visualization

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
KerkoCite.ItemAlsoKnownAs: 10/gftr32 2339240:CKY3C4AK 2405685:7I9NQ7GL
Keywords: ___working_potential_duplicate

Variables affecting teachers' attitudes towards inclusive education in Bangladesh - Ahmmed, Masud; Sharma, Umesh; Deppeler, Joanne (Journal of Research in Special Educational Needs, 2012)
Inclusive education is a worldwide reform strategy intended to include students with different abilities in mainstream regular schools. Evidence from previous research shows that success in implementing effective inclusive teaching practices in the school is contingent on teachers' positive attitudes towards inclusive education. This study was conducted in the context of primary education in Bangladesh aiming to examine variables influencing teachers' attitudes towards inclusion of students with disabilities in regular classrooms. Data for the study was collected from 738 teachers working in 293 government primary schools in Bangladesh. The results indicated that perceived school support for inclusive teaching practices and a range of demographic variables including previous success in teaching students with disabilities and contact with a student with a disability were associated with more positive attitudes of the teachers towards the inclusive education. The results are discussed with possible implications for educators, policy-makers and international organisations working on the implementation of inclusive education. © 2012 The Authors. Journal of Research in Special Educational Needs
KerkoCite.ItemAlsoKnownAs: 10.1111/j.1471-3802.2011.01226.x 2339240:EJGQITXV 2405685:KJHBE65X

Audio Lessons Through Radio for Primary Education Set for Launch -With Support from UNESCO CapED Programme for COVID-19 Educational Response for Bangladesh - UNESCO (UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:I7MG6YLA 2405685:Q34TK2MX

TV-Based Learning in Bangladesh: Is it Reaching Students? - World Bank (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:CCPPQ9BH 2405685:KWVCWU5L
Keywords: ___working_potential_duplicate

Bangladesh Data - World Bank
KerkoCite.ItemAlsoKnownAs: 2339240:3US9GRJC 2405685:NUJUM2P3

Factors in Mathematics Teachers’ Access to Digital Technologies and Their Professional Development Through Praxis in Marginalised Communities in Bangladesh - Kukulska-Hulme, Agnes; Power, Tom; Dawadi, Saraswati; Rahman, S M Hafizur; Parvin, Tauhida (Journal of Technology and Teacher Education, 2024)
The paper presents findings from a research study of 318 mathematics teachers’ experiences of access to, and use of, digital technology in their professional development in marginalised communities in ten districts across Bangladesh. The innovative two-cycle qualitative study design involved early career researchers collaborating with peer-researcher teachers who interviewed their peers about local teachers’ experiences. The interview data was analysed through the lens of Van Dijk’s model of digital access and use, addressing motivation, physical access, skills, and usage. The findings reveal that most rural teachers were able to overcome barriers to access and complete the online course using their mobile phones, but the aim of making mathematics learning more active and joyful was only realised among the minority of teachers who had a supportive school environment. Promoting and supporting opportunities for praxis in schools is essential if technology enhanced professional development is to lead to improvements in teaching and learning. The findings have important implications for practice and at policy level to rethink access to professional development through ‘mobile first’ technologies and support for praxis in schools, in marginalised communities in Bangladesh and elsewhere.
KerkoCite.ItemAlsoKnownAs: 10.70725/918790tkfksp 2405685:U2RKX6JN

School-based teachers’ professional development through technology-enhanced learning in Bangladesh - Shohel, M.; Mahruf, C.; Banks, Frank (Teacher Development)
KerkoCite.ItemAlsoKnownAs: 10.1080/13664530.2012.668103 2339240:IUEVL3KI 2405685:JAQU2MX6

Prottoy: A smart phone based mobile application to detect autism of children in bangladesh - Satu, Md. Shahriare; Azad, Md. Saikat; Haque, Md. Fardin; Imtiaz, Syed Khalid; Akter, Tania; Barua, Lipika; Rashid, Mamunur; Soron, Tanjir Rashid; Al Mamun, Khondaker Abdullah (2019 4th International Conference on Electrical Information and Communication Technology (EICT), 2019)
In developing countries, autism is needed to detect at early ages that helps us to improve the conditions of children. The diagnosis of autism is a challenging issue in the low and middle income countries due to lack of trained professionals, low cost available tools and infrastructure. In this paper, we proposed a mobile interactive automated application named prottoy to screen autism between 3 to 11 years children using Bengali version of Childhood Autism Spectrum Test. It was translated into Bengali by following cross cultural validation schemes. Pictorial representation of each question was placed into this apps. So, parents can easily check autism of their children by understanding the scenarios of each question. After screening, this app is automatically manipulated user response and detected the possibility of autism of their children. We expect that this app will promote screening that help us to detect autism early of the children in Bangladesh.
KerkoCite.ItemAlsoKnownAs: 10.1109/EICT48899.2019.9068815 2339240:37SAYW3L 2405685:54F3DEIP
Keywords: Autism; CAST; Cloud computing; Cultural differences; Pediatrics; Three-dimensional displays; Tools; Visualization; autism; detection; mobile apps; screening

A Simulation of COVID-19 School Closure Impact on Student Learning in Bangladesh [Report] - Rahman, Tashmina; Sharma, Uttam (World Bank, 2021)
This Note presents results from a series of simulations that aim to capture the impacts that school closures in Bangladesh might have on the learning levels, enrollment and future earnings of children and students using a methodological tool developed by the Education Global Practice of the World Bank . We find that overall loss in learning for every child enrolled in school even in the most optimistic scenario is expected to be substantial and the economic implications of the learning losses are huge. Available data also indicates that remote learning requires to be made more effective. It is hoped that the insights from this note will be useful for the government, non-government, private sector and civil society engaged in education service delivery as they are attempting to forge effective partnerships during and after the crisis. There is an urgent need to substantially reduce additional dropouts and absenteeism through stipends and safe school opening and communication campaigns.
Accepted: 2021-01-25T16:58:03Z KerkoCite.ItemAlsoKnownAs: 2339240:A2JMJBKU 2405685:TU8UCJ3G
Keywords: Coronavirus; Covid-19; Distance Learning; Education Quality; Pandemic Impact; Primary Education; School Closure; School Dropout; Secondary Education; Student Learning

‘When Will You Start Teaching the REAL Curriculum?’ - Karim, Azmina; Hussain, Faheem (Information and Communication Technologies for Development. Strengthening Southern-Driven Cooperation as a Catalyst for ICT4D, 2019)
This paper explores key problems faced by different humanitarian agencies in educating Rohingya refugees from Myanmar seeking asylum in Bangladesh. The first half this research provides an overview of the challenges faced by different refugee communities globally in the Education sector, followed by the relevant ICT interventions. Then, based on our interviews and focus group discussions with Rohingya refugees, we highlight the roadblocks faced by them while accessing education services in their camps. Absence of coherent curriculum, challenges with language, lack of qualified teachers, and non-acceptance of ICTs as primary education tools for children are identified as some of the key challenges faced by Rohingyas. Based on our research, we recommend that enabling policies and an inclusive hybrid knowledge network, emboldened by pre and in-service teacher training, inclusive religious education, standardized curriculum, and tangible employment opportunities can pave the path for a better and an educated future for the persecuted Rohingyas.
shortDOI: 10/ggtbq5 KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-18400-1_55 10/ggtbq5 2339240:6N8GWXWK 2405685:4FDS64G6
Keywords: Google Scholar/ "refugee education" ICT; RER theme_durable solutions

Teachers’ perceived usefulness and perceived ease of use of technology in primary school classrooms in Bangladesh - Zaman, R.A.; Raqib, A.B.M.A.; Sadek, M.A. (Teacher's World: Journal of Education and Research, 2023)
The study aimed to investigate primary school teachers’ knowledge, attitudes, and practices (KAP) regarding technology use in the classroom in five selected districts of Bangladesh. Data was collected through in-depth interviews and focus group discussions with primary school teachers, local education officers, and PTI and URC instructors. Incorporating the theoretical lens of the Technology Acceptance Model (TAM), the study examined the perceived usefulness (PU) and perceived ease-of-use (PEOU) of ICT among teachers. Findings indicated that while teachers recognize the high usefulness of ICT in educational settings, they report lower ease-ofuse, often attributable to factors like inadequate training, infrastructure and limited resources. Technology-based teaching and learning activities could enhance the quality of education and promote equity and inclusiveness in primary schools. The COVID-19 pandemic significantly influenced ICT practice in government primary schools, leading to the adoption of mobilebased teaching-learning practices. The study recommends targeted interventions emphasizing comprehensive teacher training, infrastructural enhancements, and motivational strategies are crucial to bridge the policy-practice gap regarding ICT.
KerkoCite.ItemAlsoKnownAs: 10.3329/twjer.v49i2.71992 2339240:JRW6GSQP 2405685:L7WX9WJZ

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10604329 ZenodoArchiveConcept: 10604328 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080685 10.53832/edtechhub.1005 2405685:GXMUGXHE 2405685:RK44C9BZ
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTech Horizon Scan: Rapid scan of online safety in education - Mazari, Haani; Kaye, Tom (EdTech Hub, 2022)
This EdTech Horizon Scan examines the issue of online safety in digital education — why it should be prioritised, how it is currently being approached, and its potential to become central to education design in low- and middle-income countries. Given that the internet has no borders, there is much to be done to address online safety in all parts of the world — high-income and low- and middle-income countries alike. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7336710 ZenodoArchiveConcept: 7336709 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7336710 10.53832/edtechhub.0136 2339240:4TCBX2GH 2405685:3QBCENK5 2405685:AWHK2L8L
Keywords: _r:AddedByZotZen

ঘরে বসেই শিক্ষা - EduHub Bangladesh (LearnFromHome, 2020)
ঘরে বসেই শিক্ষা
KerkoCite.ItemAlsoKnownAs: 2339240:8GSQEBBW 2405685:5FBPQTZ8

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
Examples of mobile phones being used with teachers to provide continuing professional development (CPD) in emerging economies at scale are largely absent from the research literature. We outline English in Action’s (EIA) model for providing 80,000 teachers with CPD to improve their communicative language teaching in Bangladesh over nine years. EIA’s CPD program is delivered face to face and supported through open distance learning (ODL). This innovative model of teacher CPD is supported through peer learning and self-study using a variety of print, audio and video resources. Drawing on the success of EIA’s pilot studies, where internal and external evaluation reported significant improvement in teachers’ and students’ English-language competence after one year, the current phase is using low-cost mobile phones, or the ‘trainer in your pocket’ to deliver CPD to 12,500 teachers through 2015. We believe EIA’s teacher CDP model is best suited to assist the project in achieving one of its primary goals: to increase the English-language proficiency of 12 million students, allowing them to access greater social and economic opportunities in the future. We argue EIA’s use of mobile phones for the provision of teacher CPD – at scale – is timely and replicable in both developed and developing contexts.
Publisher: Routledge _eprint: https://doi.org/10.1080/19415257.2013.766232 KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2013.766232 2339240:4SYER8H6 2405685:3WMSFI3D
Keywords: English in Action; communicative language teaching; mobile phones; open distance learning; school-based professional development (SBPD); teachers’ continuing professional development (CPD)

Cyber Security Ordinance - Government of Bangladesh (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:DL585RS8 2405685:76QZX597

Personal Data Protection Ordinance [Draft] - Government of Bangladesh (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:9IXHFYSX 2405685:J9F6G7QT

National ICT Policy 2018 - Government of Bangladesh (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:H56MA5IU 2405685:2X3HT3PX

Parenting and child’s (five years to eighteen years) digital game addiction: A qualitative study in North-Western part of Bangladesh - Keya, Farah Deba; Rahman, Md Mostafizur; Nur, M. Tareq; Pasa, Md Kamal (Computers in Human Behavior Reports, 2020)
Globally, addiction to digital game among the children and adolescents is a growing concern due to its increasing rate of users and adverse effects on their personal including health and social life. Reviewing the literatures shows a number of factors for child’s digital game addiction. Of the literatures, only a few plausibly shows some form of parenting be a cause for digital game addiction, but under what conditions of parenting influence child to be addicted to digital game is not adequately addressed. Aiming to address the gap, a qualitative study was conducted in North-western Bangladesh using Ethnographic Interview with children and Indepth Interview with parents. The data was analyzed manually following thematic framework. The result of the study shows troubled child-parent relationship and parental attitudes for making their child competitive in education, parental neglect, loneliness and anxiety of the child, and permissive parenting are attributed to digital game addiction. Its social basis is emanated from the family’s asymmetrical role in a market based society. Making a child competitive and capable for future market system is over prioritized, whereas providing emotional security is undermined. It also argued that in a capitalistic society, parents has turned tobe a less authoritative figure to deal children’s issue due to the father’s inability to address economic needs of the family adequately and mothers’ economic dependence to their male counter-part. In such a context, parents are compelled to minimize the gap by offering or allowing child to digital game and so gradually children become addicted to digital game. This argument supported the idea of Frankfurt school on how people attracted and depended on culture industry.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.chbr.2020.100031 2339240:EMRM4CEY 2405685:FML9MHFG
Keywords: Digital game addiction; Economic pressure; Emotional security; Parental neglect; Permissive parenting; Troubled child-parent relationship

Futures of Education in Bangladesh: Envisioning 2041 - a2i (Government of People's Republic of Bangladesh, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:WBR2EN8Q 2405685:HTABJ4F4

Dropout at primary and secondary level: a challenge to ensure rights to education for the Government of Bangladesh - Zaman, Md. Mostafa (Institute of Governance Studies (IGS), BRAC University, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:9C2DZWV7 2405685:MWALFWUF

Introducing mobile technology for enhancing teaching and learning in Bangladesh: teacher perspectives - Shohel, M. Mahruf C.; Power, Tom (Open Learning: The Journal of Open, Distance and e-Learning, 2010)
This paper reviews the themes emerging from Bangladeshi teachers' experiences of taking part in the initial research and the development stage of a professional development programme they were involved with. The Secondary Teaching and Learning Programme is an information and communications technologies-enhanced supported open distance learning programme of professional development in English-language teaching. This paper presents evidence arising from semi-structured interviews carried out with teachers from a pre-pilot study for the English in Action project. The teachers participating in this study reflect upon six months' experience of using professional development materials (course material of audio podcasts enhanced with text and images; videos of classroom practice; audio of classroom language) and classroom resources (audio recordings of text-book reading passages, songs, poems and stories), all accessed via portable digital media players (iPods). (Contains 1 table and 1 figure.)
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 325 Chestnut Street Suite 800, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/815957037?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/02680513.2010.511953 10/brrchv 2339240:9GRACLAU 2405685:BFA3BZUN 2534378:HMHCMR9X 2534378:KT2WCVFZ 2534378:QXQHZY9I 2534378:UJQAALFW 2534378:ZJT5CTY3
Keywords: BANGLADESH; Bangladesh; COMPUTER assisted language instruction; COMPUTERS in education; CONTINUING education; Computer Assisted Instruction; DISTANCE education; Developing Nations; Digital audio players; Distance Education; Distance learning; ENGLISH language – Study & teaching – Foreign speakers; ERIC; Current Index to Journals in Education (CIJE); Education–Teaching Methods And Curriculum; Educational Development; Educational Technology; Educational technology; Elementary Secondary Education; English (Second Language); English in Action support model; English language; Foreign Countries; Handheld Devices; Higher Education; Inservice Teacher Education; Interviews; LANGUAGE teachers; Language instruction; Multimedia Instruction; OPEN learning; Open Universities; Pilot Projects; Postsecondary Education; Professional development; Program Descriptions; Program Development; Program Effectiveness; Protocol Materials; SECONDARY education; Second Language Instruction; Secondary Education; Secondary School Teachers; Studies; TEACHER development; TEACHERS – Attitudes; TELEMATICS; Teacher Attitudes; Teachers; Technology Integration; United Kingdom; Video Technology; _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2098161; ___working_potential_duplicate; __finaldtb; auto_merged; mobile learning; mobile technology; technology intervention

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

Household Income and Expenditure Survey 2016-2017 - BBS (Bangladesh Bureau of Statistics, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:5FKNQZYC 2405685:T7SBCC5A

National Education Policy 2010 - MoE (Ministry of Education Government of the People's Republic of Bangladesh, 2010)
KerkoCite.ItemAlsoKnownAs: 2339240:UTLS7RYN 2405685:6I47IM2H

Characteristics of effective teacher education in low- and middle-income countries: an overview (HDR10A) - Haßler, Björn; McBurnie, Chris; Allier-Gagneur, Zoe; Damani, Kalifa (EdTech Hub, 2020)
previousDOI: 10.5281/zenodo.3873458 EdTechHub.Copy: 2129771:2BEHBMUH EdTechHub.Copy: 2129771:2BEHBMUH EdTechHub.Copy: 2129771:C6TREICJ EdTechHub.Copy: 2129771:C6TREICJ EdTechHub.Source: 2405685:HFKVA2IQ EdTechHub.Source: <this> KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3873458 10.53832/edtechhub.0006 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

COVID-19 Response and Recovery Plan - Ministry of Primary and Mass Education (Government of People's Republic of Bangladesh, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:433RGDYT 2339240:6Q5BVEZA 2339240:GJLEVTTL 2405685:52CDSLIM 2405685:8KHDLPVL 2405685:SV9HP48X

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4540204 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4540204 10.5281/zenodo.4540204 2339240:26GYDUTU 2339240:2Q9AWGM3 2339240:IQ36IBT8 2339240:MDUWMNQ5 2339240:P9XQBBQC 2405685:856UY54Y 2405685:CZZ5WHT7 2405685:P9T68ACJ 2405685:UGZDH4LB
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

How to re-imagine learning in the wake of Covid-19 (EdTech Hub, 2020)
Last week the EdTech Hub, #NextGenEdu, and Education Development Trust convened experts, policymakers, and implementers to discuss their visions for a reimagined approach to learning in the wake of coronavirus. The invited speakers were: Mohibul Hasan Chowdhury, Deputy Minister of Education, Bangladesh Ministry of Education Jim Ackers, Regional Education Advisor, UNICEF South Asia Regional Office Sonam Wangchuk, Founder, Students’ Educational…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707880 2405685:KDWC5B3N
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

New Brief: Monitoring Distance Learning During the Covid-19 Pandemic - Bashir, Amreen; Groeneveld, Caspar; Kaye, Tom (EdTech Hub, 2020)
In the initial rush to respond to school closures, countries focused on rolling out distance education. Policy-makers now realise that effective distance education requires robust data generated via high-quality monitoring. This blog highlights the findings of a brief synthesising effective practices in monitoring distance education. Since March 2020, the Covid-19 pandemic has impacted 36 million learners in Bangladesh. Schools closed…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4708238 2405685:73G8TGWV
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

Millions of Bangladeshis learn English with BBC Janala - BBC (2014)
From 2005-2014, BBC Janala ("window" in Bangla) was a unique service unlocking access to English language learning for millions of people in Bangladesh.
KerkoCite.ItemAlsoKnownAs: 2339240:SEHN95DH 2405685:CW86V3PW

Annual Primary School Census 2019 (Draft) - MoPME; Directorate of Primary Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:HALFYWI8 2405685:LEVHI9LQ

Dearth of research in Bangladeshi universities - Momin, S (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:X9NZ9GIQ 2405685:B5DNCPYF

Countries by Density - World Population Review (World Population Review, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QLHYHSIQ 2405685:S4R4KANR

Population by Country - Worldometer (World Population Review, 2021)
List of countries and dependencies in the world ranked by population, from the most populated. Growth rate, median age, fertility rate, area, density, population density, urbanization, urban population, share of world population.
KerkoCite.ItemAlsoKnownAs: 2339240:SI7BVSX4 2405685:A3INEC8H

Quality, continuity for primary education - UNICEF (UNICEF)
KerkoCite.ItemAlsoKnownAs: 2339240:DIUI995Z 2405685:P3S2Q9QR

Recovery of Learning Loss Created Due to COVID-19 Crisis: Analysis of Bangla Learning Outcomes and Identification of Content - NAPE; Room to Read (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:6BFW7CPF 2405685:3WDEFT65

Report On Assessment Of ‘multimediaclassrooms (Mmc) And Teacher- Led Content Development’ - a2i (Access to Information (a2i) Programme, 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:N6B3CKKB 2405685:QB2ZC7VP

2018 Civil Society Organization Sustainability Index - for Asia 5th Edition – December 2019 - USAID (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:SA6U2LEK 2405685:3ILYUE9N

a2i website - a2i
KerkoCite.ItemAlsoKnownAs: 2339240:IIXB7B8P 2405685:WH4GL8JP

2019 Civil Society Organization Sustainability Index - for Asia 6th Edition – December 2020 - USAID (United States Agency for International Development Bureau for Democracy, Conflict and Humanitarian Assistance Center of Excellence on Democracy, Human Rights and Governance, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:9L542D8M 2405685:2GPSJK4R

A Study on Implementation of `ICT in Education Training’ in Government Primary Schools - Haque, Z; Sarker, D; Rahman, Md; Ohiduzzaman, K; Ahammed, S; Islam, Md; Hasan, M (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:YPSRY3QV 2405685:WYITTZMP

Computer-Aided Learning and Mentoring for Improvement of Teaching Quality: An Assessment of BRAC Interventions - Sharmin, Nazia; Roy, Goutam (SSRN Electronic Journal, 2011)
Methods and materials 3 Research area and sampling 3 Variables 4 Data collection techniques and tools 4 Field operation 4 Ethical consideration 4 Data management and analysis 4 Results 5 Computer-aided learning (CAL) 5 Mentoring 10 Conclusion
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.2923676 10/gkm64r 2339240:UPMNTBZ3 2405685:UUD9ZMX7

Aid Effectiveness and Policy Ownership - Sobhan, R (Development and Change, 2002)
KerkoCite.ItemAlsoKnownAs: 10.1111/1467-7660.00267 10/dqm388 2339240:4NCLWIGB 2405685:ZMMG5MJL

UNICEF scales up support to keep children learning, as COVID-19 forces schools to close - UNICEF (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:7R2QCCFC 2405685:A5P8SUV9

Understanding the relationship between teachers’ pedagogical beliefs and technology use in education: a systematic review of qualitative evidence - Tondeur, Jo; van Braak, Johan; Ertmer, Peggy A.; Ottenbreit-Leftwich, Anne (Educational Technology Research and Development, 2017)
This review was designed to further our understanding of the link between teachers’ pedagogical beliefs and their educational uses of technology. The synthesis of qualitative ﬁndings integrates the available evidence about this relationship with the ultimate goal being to facilitate the integration of technology in education. A meta-aggregative approach was utilized to analyze the results of the 14 selected studies. The ﬁndings are reported in terms of ﬁve synthesis statements, describing (1) the bi-directional relationship between pedagogical beliefs and technology use, (2) teachers’ beliefs as perceived barriers, (3) the association between speciﬁc beliefs with types of technology use, (4) the role of beliefs in professional development, and (5) the importance of the school context. By interpreting the results of the review, recommendations are provided for practitioners, policy makers, and researchers focusing on pre- and in-service teacher technology training.
KerkoCite.ItemAlsoKnownAs: 10.1007/s11423-016-9481-2 10/gbgzn4 2339240:ZFEQC5I7 2405685:HIV77NKT

Country Overview: Bangladesh - Rogers, Mike (GSMA, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:JVDAQ8RC 2405685:V38NVLIS

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5602863 10.53832/edtechhub.0063 2339240:I3JETHDB 2405685:5ZF9VGMK 2405685:6P5Q5IRZ 2405685:BIRTYTRC
Keywords: _r:AddedByZotZen

Shikho aims to bring in the AI hype to ed-tech—here’s how - Monamee, Maisha Islam (The Daily Star, 2025)
Shikho, a Bangladesh-based edtech company, has recently introduced a beta version of Shikho AI, an artificial intelligence tool aimed at addressing educational gaps for Bangla-speaking students.
KerkoCite.ItemAlsoKnownAs: 2339240:LNKMF6JB 2405685:HHD2M6FG

Shikho aims to bring in the AI hype to ed-tech—here’s how - Monamee, Maisha Islam (The Daily Star, 2025)
Shikho, a Bangladesh-based edtech company, has recently introduced a beta version of Shikho AI, an artificial intelligence tool aimed at addressing educational gaps for Bangla-speaking students.
KerkoCite.ItemAlsoKnownAs: 2339240:LNKMF6JB 2405685:HHD2M6FG

Effective Assessment and Progress Monitoring in an Online Environment: A Study in Six Countries - T4 Education; EdTech Hub (EdTech Hub, 2022)
The study was undertaken in six countries – Bangladesh, India, Nigeria, Pakistan, Philippines, and South Africa. The data collection involved focus group discussions with two held in each country..
KerkoCite.ItemAlsoKnownAs: 2339240:PA9TD6UB 2405685:E66UZCLZ

Spotlight on Edtech: Bangladesh - Gonchigodorj, Ariunkhishig; Warren, Frederika; Bapna, Akanksha; Sharma, Namrata; Pellini, Arnaldo; Green, Crystal (HundrED, 2023)
HundrED is a mission-driven organisation helping every child flourish through education innovation
KerkoCite.ItemAlsoKnownAs: 2339240:PVMPLKYV 2405685:2VILZQ6S

BRAC Education Programme Bangladesh - BRAC (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:V9ITPR43 2405685:QBPVDD4B

Bangladesh educational assessment: pre-primary and primary Madrasah education in Bangladesh - Abdalla, Amr; Raisuddin, A. N. M.; Hussein, Suieiman (Basic Education and Policy Support (BEPS) Activity, United States Agency for International Development, 2004)
KerkoCite.ItemAlsoKnownAs: 2339240:67Z7UAAE 2405685:BAGTSLQM

Govt turns to AI for faster delivery of projects - Byron, Rejaul Karim (The Daily Star, 2025)
Bangladesh plans to launch a Tk 316 crore reform programme aimed at significantly speeding up project planning, approval, and implementation through the use of artificial intelligence for the first time.
KerkoCite.ItemAlsoKnownAs: 2339240:25VSHPL3 2405685:54LDYNL8

AI use cases of Bangladesh - Chowdhury, Anir (2024)
KerkoCite.ItemAlsoKnownAs: 2339240:HQBGPSCX 2405685:CZRL77KB

Advancing AI Ethics in Bangladesh - UNESCO (UNESCO, 2024)
Artificial Intelligence (AI) has become essential in our daily lives, influencing sectors such as healthcare, education, and governance. However, with its immense capabilities comes the responsibility to use it sensibly. Ensuring that AI is developed and deployed ethically is crucial to prevent harm and ensure it benefits society positively. Recognizing this importance, UNESCO (United Nations Educational, Scientific and Cultural Organization) has taken significant steps to address AI ethics through its Recommendation on the Ethics of AI, which provides guidelines to promote the responsible use of AI, safeguarding human rights, and promoting societal well-being.
KerkoCite.ItemAlsoKnownAs: 2339240:S287ZCV8 2405685:TLPU79WH

Behind Bangladesh’s Protests: Rising Frustration - Bhattacherjee, Aparupa (The Diplomat)
KerkoCite.ItemAlsoKnownAs: 2339240:8HEZ3QGI 2405685:3RQWC5AE

Bangladesh GNI per capita 1973-2021 - Macrotrends
GNI per capita (formerly GNP per capita) is the gross national income, converted to U.S. dollars using the World Bank Atlas method, divided by the midyear population. GNI is the sum of value added by all resident producers plus any product taxes (less subsidies) not included in the valuation of output plus net receipts of primary income (compensation of employees and property income) from abroad. GNI, calculated in national currency, is usually converted to U.S. dollars at official exchange rates for comparisons across economies, although an alternative rate is used when the official exchange rate is judged to diverge by an exceptionally large margin from the rate actually applied in international transactions. To smooth fluctuations in prices and exchange rates, a special Atlas method of conversion is used by the World Bank. This applies a conversion factor that averages the exchange rate for a given year and the two preceding years, adjusted for differences in rates of inflation between the country, and through 2000, the G-5 countries (France, Germany, Japan, the United Kingdom, and the United States). From 2001, these countries include the Euro area, Japan, the United Kingdom, and the United States.
KerkoCite.ItemAlsoKnownAs: 2339240:ACPLQN5F 2405685:SDGDR87J

Covid-19 disrupts education in rural Bangladesh - Uttom, Stephan; Rozario, Rock (UCA News, 2020)
Pupils and teachers lament lack of access to online classes due to poverty
KerkoCite.ItemAlsoKnownAs: 2339240:Z2PZ4JBN 2405685:P9WN6HSY

Bangladesh - Third Primary Education Development Program (English) - World Bank Group (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:XHXPR2HZ 2405685:CTXR6F8P

Achieving mobile-enabled digital inclusion in Bangladesh - GSMA (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:668LBR98 2405685:W5VR72AL

Bangladesh: flexible learning for slum dwelling children - Children on the Edge (Children on the Edge)
Together with our partner MUKTI, we support nine Community Schools specifically set up to help working children in the Cox’s Bazar beach area.
KerkoCite.ItemAlsoKnownAs: 2339240:WRIZVD8C 2405685:2C6YIXPH

Mobile Phone Subscribers in Bangladesh February, 2020 | BTRC - BTRC
KerkoCite.ItemAlsoKnownAs: 2339240:XA5TS6HH 2405685:J7IZMF9T

Realising Affordable Internet in Bangladesh: A Case Study - Shadrach, B. (Alliance for Affordable Internet A4AI, 2016)
KerkoCite.ItemAlsoKnownAs: 2339240:FYPZUJF2 2405685:PPY8SALG

UNESCO Data for the Sustainable Development Goals: Bangladesh - UNESCO
KerkoCite.ItemAlsoKnownAs: 2339240:4T9RZ2PL 2405685:DDQRPTDD

TV-Based Learning in Bangladesh: Is it Reaching Students? - World Bank (World Bank Group, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:286IGBN6 2405685:GAPR3LZN
Keywords: ___working_potential_duplicate

The Future of Digital in Bangladesh Digital Readiness Assessment - Jahangir, Zulkarin; Safir, Abdullah Hassan; Ahmed, Shamael (BRAC Institute of Governance and Development (BIGD), 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:EU63K26F 2405685:243CQYRH

Crisis-Led Approaches to Teaching and Learning in Bangladesh - Khan, Maluba; Smith, Thomas; Islam, Mohammed Zakiul; Anand, Kusha; Hossain, Tahrima; Ahmed, Shakil; Islam, Rakibul; Atuly, Afsana Sadiq; Nayeem, Azwa; Sabbab, Salman; Hassan, Mehdi; Sarwar, Afzal Hossain (Cardiff University, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:X6A6NBMS 2405685:JSN76N4D
Keywords: ⛔ No INSPIRE recid found

TV-Based-Learning-in-Bangladesh-Is-it-Reaching-Students.pdf
KerkoCite.ItemAlsoKnownAs: 2405685:SERJWUI6

Bangladesh Primary Education Annual Sector Performance Report (ASPR) 2019 - Directorate of Primary Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BCNM4PNJ 2405685:CW438FLX

Bangladesh Demographic and Health Survey 2017-2018: key indicators - NIPORT; ICF (National Institute of Population Research and Training (NIPORT) and ICF, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:77QXWVJP 2405685:2IGTN5VN

Exploring the fundamental factors of digital inequality in Bangladesh - Islam, Muhammad Nazrul; Inan, Toki Tahmid (SAGE Open, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1177/21582440211021407 2339240:C3ZIMHJY 2405685:TDV2W3I9

The state of education in urban slums of Bangladesh - Khondoker, Zarine Anan (BRAC Institute of Governance and Development, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:KQ6BMYBH 2405685:BWLXUGA2

Local governance, decentralisation and corruption in Bangladesh and Nigeria - Nixon, Hamish A D; Menocal, Alina Rocha; Bhattacharya, Debapriya; Fuad, Syed Muhtasim; Hassan, Idayat; Iwuamadi, Kelechi C; Rezbana, Umme Shefa; Yusuf, Shamsudeen (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:BT5PUL3H 2405685:6LBMHHTG 4656463:VP5TVEFF
Keywords: ⛔ No DOI found

Education Budget of Bangladesh: Investing resources for improved learning outcomes - Khatun, Fahmida; Saadat, Syed Yusuf; Mahbub, Afrin (Centre for Policy Dialogue, 2024)
KerkoCite.ItemAlsoKnownAs: 2339240:6WNIRJWT 2405685:YSFHX6BB
Keywords: ⛔ No DOI found

The Key Informant Child Disability Project in Bangladesh and Pakistan - Mactaggart, I (London School of Hygiene and Tropical Medicine, 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:D8CIW7KU 2405685:JCNFYGSX

EdTech, Learning and Equity: The EdTech Hub Research Portfolio - Haßler, Björn; Wagner, Dan; Outhwaite, Laura (EdTechHub, 2023)
ZenodoArchiveID: 10079721 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1000 ZenodoArchiveConcept: 10079720
Keywords: _internal; _r:AddedByMyEducationEvidence

The role of government and NGOs in slum development: the case of Dhaka City - Habib, Enamul (Development in Practice, 2009)
This article addresses the situation of slums in Dhaka City in relation to government and NGO mechanisms and priorities for slum development and upgrading. It concludes with specific suggestions for better slum management in the Bangladesh capital.
Publisher: [Taylor & Francis, Ltd., Oxfam GB] KerkoCite.ItemAlsoKnownAs: 10.1080/09614520802689576 2339240:V34LB5LZ 2405685:UMWM9PHR

Telementoring and homeschooling during school closures: A randomized experiment in rural Bangladesh - Hassan, Hashibul; Islam, Asad; Siddique, Abu; Wang, Liang Choon (Centre for Development Economics and Sustainability, 2021)
Prolonged school closures due to political unrests, teacher strikes, natural disasters, and public health crises can be detrimental to student learning in developing countries. Using a randomized controlled experiment in 200 Bangladeshi villages, we evaluate the impact of over-the-phone mentoring and homeschooling support delivered by volunteers on the learning outcomes of primary school children during school closures caused by the coronavirus pandemic. The telementoring program improved the learning outcomes of treated children by 0.75 SD and increased homeschooling involvement of treated mothers by 0.64 SD. The impacts on learning are driven primarily by the direct mentoring of children and to some extent also by the increased homeschooling involvement of mothers. Academically weaker children and households from relatively lower socioeconomic backgrounds benefitted the most from telementoring. These findings suggest that learning crises in low-resource settings can be addressed by simple and very low-cost technology solutions.
KerkoCite.ItemAlsoKnownAs: 2339240:5YSHGI3S 2339240:7WBML8RC 2405685:6J9MZIZY 2405685:XE45G75X 2405685:XU7PCDNA 2534379:RF4FNWBS
Keywords: ___working_potential_duplicate

Telementoring and homeschooling during school closures: A randomized experiment in rural Bangladesh - Hassan, Hashibul; Islam, Asad; Siddique, Abu; Wang, Liang Choon (SocArXiv, 2022)
Using a randomized controlled experiment in 200 Bangladeshi villages, we evaluate the impact of over-the-phone mentoring and homeschooling support delivered by volunteers on the learning outcomes of primary school children during school closures caused by the coronavirus pandemic. The telementoring program improved the learning outcomes of treated children by 0.75 SD and increased homeschooling involvement of treated mothers by 0.64 SD. The impacts on learning are driven primarily by the direct mentoring of children and to some extent also by the increased homeschooling involvement of mothers. Academically weaker children and households from lower socioeconomic backgrounds benefitted the most from telementoring.
KerkoCite.ItemAlsoKnownAs: 10.31235/osf.io/mhyq5 2339240:9PH6DMPD 2405685:PADF6IYS

Generative AI in education: Current state, future directions, and implications in Bangladesh - Tasnim, Maisha (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:BUUUTRS7 2405685:Y4JWRMYZ

Making Vision 2041 a Reality: Perspective Plan for Bangladesh 2021-2041 - General Economics Division (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:4SPHEM5B 2405685:T8I5MW3K

Telementoring and homeschooling during school closures: A randomized experiment in rural Bangladesh - Hassan, Hashibul; Islam, Asad; Siddique, Abu; Wang, Liang Choon (SocArXiv, 2022)
Using a randomized controlled experiment in 200 Bangladeshi villages, we evaluate the impact of over-the-phone mentoring and homeschooling support delivered by volunteers on the learning outcomes of primary school children during school closures caused by the coronavirus pandemic. The telementoring program improved the learning outcomes of treated children by 0.75 SD and increased homeschooling involvement of treated mothers by 0.64 SD. The impacts on learning are driven primarily by the direct mentoring of children and to some extent also by the increased homeschooling involvement of mothers. Academically weaker children and households from lower socioeconomic backgrounds benefitted the most from telementoring.
KerkoCite.ItemAlsoKnownAs: 10.31235/osf.io/mhyq5 2339240:9PH6DMPD 2405685:PADF6IYS

Autism Barta — A smart device based automated autism screening tool for Bangladesh - Bardhan, S.; Mridha, G. M. Monjur Morshed; Ahmed, E.; Ullah, M. A.; Ahmed, H. U.; Akhter, S.; Rabbani, M. G.; Mamun, K. A. Al (2016 5th International Conference on Informatics, Electronics and Vision (ICIEV), 2016)
Journal Abbreviation: 2016 5th International Conference on Informatics, Electronics and Vision (ICIEV) KerkoCite.ItemAlsoKnownAs: 10.1109/ICIEV.2016.7760073 2339240:2T9KYHRK 2405685:23HWNUMS

Data Privacy in Bangladesh A Review of Three Key Stakeholders Perspectives - Hossain, Kamal; Alam, Khabirul; Khan, Umme Saara (Seventh International Conference on Advances in Social Science, Economics and Management Study - SEM 2018, 2018)
KerkoCite.ItemAlsoKnownAs: 10.15224/978-1-63248-164-1-32 2339240:KCTEUWP5 2405685:B99HJAAP

Access to and exclusion from primary education in slums of Dhaka, Bangladesh - Cameron, Stuart (2010)
OCLC: 749900177 Consortium for Research on Educational Access, Transitions and Equity KerkoCite.ItemAlsoKnownAs: 2339240:5C85GC9N 2405685:9GI5WMTR

Education sector plan (ESP) for Bangladesh Fiscal years 2020/21-2024/25 - Ministry of Education (Ministry of Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:WE7ZPX8W 2405685:WRBA628Y

Education Sector Plan (ESP) for Bangladesh Fiscal Years 2020/21-2024/25 - MoE (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:XHUT23N9 2405685:MWK38D4Z

COVID 19, Technology-based Education and Disability: The case of Bangladesh - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5B34JWFZ 2405685:7K7JA456

Telementoring and homeschooling during school closures: A randomized experiment in rural Bangladesh - Hassan, Hashibul; Islam, Asad; Siddique, Abu; Wang, Liang Choon (SocArXiv, 2022)
Using a randomized controlled experiment in 200 Bangladeshi villages, we evaluate the impact of over-the-phone mentoring and homeschooling support delivered by volunteers on the learning outcomes of primary school children during school closures caused by the coronavirus pandemic. The telementoring program improved the learning outcomes of treated children by 0.75 SD and increased homeschooling involvement of treated mothers by 0.64 SD. The impacts on learning are driven primarily by the direct mentoring of children and to some extent also by the increased homeschooling involvement of mothers. Academically weaker children and households from lower socioeconomic backgrounds benefitted the most from telementoring.
KerkoCite.ItemAlsoKnownAs: 10.31235/osf.io/mhyq5 2339240:9PH6DMPD 2405685:PADF6IYS

Summative Evaluation of GPE’s Country-Level Support to Education: Bangladesh - Universalia (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Z5GUHIPP 2405685:BJ22GNWE 4656463:3BTPTHP9

Master Plan for Information and Communication Technology in Education (2012-2021) - MoE (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:9HILNTF3 2405685:MNN7P3J6

IID at CIES 2025: Exploring AI’s role in Bangladesh’s education system - IID (IID, 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:CKE2VU87 2405685:5PVWER63

Lessons on technology-enabled teacher professional development from Bangladesh’s national curriculum reform - Ahmed, Shakil; Mazari, Haani; Hassan, Mehdi; Azam, Shafiul; Sidotam, Annie; Clarke-Wilson, Alison; Sarwar, Md Afzal Hossain (EdTech Hub, 2023)
This blog presents Part 1 of our lessons on tech-enabled professional development. We shall be bringing you more insights and evidence in Part 2. Stay tuned!
KerkoCite.ItemAlsoKnownAs: 2339240:UHDL5L94 2405685:IPRDDKZN

Bangladesh National ICT Household Survey: report and overview of main results 2018-2019 - Alliance for Affordable Internet; A2I Programme
KerkoCite.ItemAlsoKnownAs: 2339240:FWLPTEL3 2405685:2RX4URP2

Reaching the Unreached Through Open and Distance Learning (ODL) in Bangladesh, India and Pakistan - Ferreira, Frances (Commonwealth of Learning (COL), 2017)
GIRLS Inspire is a Commonwealth of Learning (COL) project established to mobilise the power of open and distance learning (ODL) to provide secondary schooling and skills development training to women and girls who are prevented from attending schools by barriers such as early marriage, cultural norms and distance from schools. This final report to the Department of Foreign Affairs and Trade (DFAT) Australia reflects on the work that has taken place since January 2016. It is framed around the project’s objectives and provides a rich account of activities that took place, presented in both quantitative and qualitative forms.
Accepted: 2017-07-08T01:14:45Z KerkoCite.ItemAlsoKnownAs: 2339240:WTLYI8A9 2405685:DBN3P8G4
Keywords: ___working_potential_duplicate

Reaching the unreached through open and distance learning (ODL) in Bangladesh, India and Pakistan - Ferreira, Frances (Commonwealth of Learning (COL), 2017)
GIRLS Inspire is a Commonwealth of Learning (COL) project established to mobilise the power of open and distance learning (ODL) to provide secondary schooling and skills development training to women and girls who are prevented from attending schools by barriers such as early marriage, cultural norms and distance from schools. This final report to the Department of Foreign Affairs and Trade (DFAT) Australia reflects on the work that has taken place since January 2016. It is framed around the project’s objectives and provides a rich account of activities that took place, presented in both quantitative and qualitative forms.
Publisher: Commonwealth of Learning (COL) KerkoCite.ItemAlsoKnownAs: 2339240:FP7JZH2X 2405685:SUVKKTP6
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Can Low-Tech Solutions Improve Rohingya Teachers' Pedagogical Skills in Cox's Bazar, Bangladesh? - Andra, Nishitha
KerkoCite.ItemAlsoKnownAs: 2339240:H8W5QYJL 2405685:XUCV6JRN

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
ZenodoArchiveID: 4706067 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706067 2339240:Y24AUHV8 2405685:I3AV65H3 2405685:WQ8HX957
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Use of Technology in Open and Distance Education: A Guideline for the Educational Institutions in Bangladesh - Islam, Saria; Mahmudul, A.S.M. (International Journal of Applied Information Systems, 2016)
KerkoCite.ItemAlsoKnownAs: 10.5120/ijais2016451481 2339240:ICM5ECYQ 2405685:A9QMZE8J

Reaching the Unreached through Open and Distance Learning (ODL) in Bangladesh, India and Pakistan: Final Report - Commonwealth of Learning (Commonwealth of Learning, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:L7RZVSRD 2405685:PXY96GW4

Revisiting the impact of covid-19 on adolescents in urban slums in Dhaka, Bangladesh: round 2 - Raha, Samira Ahmed; Rana, Sajib; Mamun, Saklain Al; Anik, Mehedi Hasan; Roy, Prantik; Alam, Farhana; Sultan, Maheen (Gender and Adolescence: Global Evidence, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WYUAE2BS 2405685:Y2LGTIPF
Keywords: ⛔ No DOI found

Understanding the first and second digital divides in rural Bangladesh: internet access, online skills, and usage - Siddiquee, Muhammad Shahadat Hossain; Islam, Md. Saiful (BRAC Institute of Governance and Development (BIGD), 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:H7E4MIUY 2405685:82R7AZNN

Overview of emerging country-level response to providing educational continuity under COVID-19: What’s working? What isn’t? - Joynes, Chris; Gibbs, Emma; Sims, Kate (2020)
ZenodoArchiveID: 4706062 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706062 2339240:IB8GIAAB 2339240:VEARRJJL 2339240:XRVLW2AX 2405685:BR48DF69 2405685:IPAT355N 2405685:SDTIZDHS
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Bangladesh - Additional Financing to the Second Reaching Out-of-School Children Project : Learning Opportunities for Displaced Rohingya Children - World Bank Group (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:XP8M9YUK 2405685:Z37EUUD9

Government expenditure on education, total (% of GDP) - South Asia, Pakistan, Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Sri Lanka | Data - World Bank (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:YTFFFUV4

Toward a holistic approach to EdTech effectiveness: Lessons from Covid-19 research in Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone - Nicolai, Susan; Jordan, Katy; Adam, Taskeen; Kaye, Tom; Myers, Christina (International Journal of Educational Development, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2023.102841 2405685:EFV98PTB

For Bangladeshi kids, 10 minute school seeks to democratise education - Future Education Magazine (2023)
According to the creators of edtech 10 Minute School, there are many disparities in education access in Bangladesh. Since many rural areas lack quality educational facilities, students must go to the capital Dhaka to study for their university entrance exams. However, only households with sufficient funds have access to that alternative.
Section: News KerkoCite.ItemAlsoKnownAs: 2339240:7Y8ZU7MZ 2405685:9QKUC32G

Quality of Education and Teacher Learning: A Review of the Literature - Leu, Elizabeth; Price-Rom, Alison (American Institutes for Research under the EQUIP1 LWA Academy for Educational Development, 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:K3KECM73 2405685:TTR5IKQQ

Creditor Reporting System (CRS) - OECD (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GKAXYNKY 2405685:QF9A6M5Z
Keywords: ___working_potential_duplicate

Open and distance learning for basic education in South Asia: its potential for hard-to-reach children and children in conflict and disaster areas. - Morpeth, R; Creed, C; Cullen, J; Page, E; Raynor, J (United Nations Children's Fund, 2009)
OCLC: 732344293 KerkoCite.ItemAlsoKnownAs: 2339240:QT6HVKXS 2405685:WLVSJWJH
Keywords: ___working_potential_duplicate

Human Development Reports - United Nations Development Programme (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:AD2VSI2P 2405685:KA8YNP9D

Innovative Strategies for Accelerated Human Resources Development in South Asia:: Information and Communication Technology for Education—Special Focus on Bangladesh, Nepal, and Sri Lanka - Asian Development Bank (Asian Development Bank, 2017)
Edition: 0 ISBN: 9789292610333 9789292610326 shortDOI: 10/ghgnfh KerkoCite.ItemAlsoKnownAs: 10.22617/TCS179080 10/ghgnfh 2339240:DC9GXZHD 2339240:H8XPPDHF 2405685:9CV4C8ZT 2405685:CIIMK9AK
Keywords: Systems Framework

Innovative strategies for accelerated human resource development in South Asia: Information and communication technology for education - Special focus on Bangladesh, Nepal, and Sri Lanka - ADB (Asian Development Bank, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:XPQH26KA 2405685:ZT5HV4GA

How many children and young people have internet access at home - UNICEF; ITU (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:T2EURV3P 2405685:E3JV6NQZ

Logic Model Development Guide (W.K. Kellogg Foundation)
Nonprofits today are being pressed to demonstrate the effectiveness of their program activities by initiating and completing outcome-oriented ...
KerkoCite.ItemAlsoKnownAs: 2339240:4W3QUW2E 2405685:AQPLLMWW

Nothing as Practical as Good Theory : Exploring Theory-Based Evaluation for Comprehensive Community Initiatives for Children and Families | Semantic Scholar - Weiss, Carol
KerkoCite.ItemAlsoKnownAs: 2339240:SNUMFGQP 2405685:ESCTB9EV

Reopening Schools - When and how - Campe (Evernote, 2021)
Timing of the survey - The survey was conducted between 7 to 22 November 2020. Slide 9 - % students who participated in distance learning in the last 2 weeks prior to the survey Primary - 31.4% Second...
KerkoCite.ItemAlsoKnownAs: 2339240:3PDAXZPR 2405685:MUJGM6QH

Theories of Change in International Development: Communication, Learning, or Accountability? - Valters, Craig (2014)
Critically analysing assumptions is a much needed endeavour in international development policy and practice: existing management tools rarely encourage critical thinking and there are considerable political, organisational and bureaucratic constraints to the promotion of learning throughout the sector. The Theory of Change approach – an increasingly popular management tool and discourse in development – hopes to change some of that. This approach explicitly aims to challenge and change implicit assumptions in world views and programme interventions in the lives of others, yet little is known about the extent to which it really does so. This paper provides a much needed analysis of how Theories of Change are used in the day-to-day practice of an international development organisation, The Asia Foundation. They use the approach in three ways: to communicate, to learn and to be held accountable, which each exist in some tension with each other. Creating Theories of Change was often found to be a helpful process by programme staff, since it provided a greater freedom to explain and analyse programme interventions. However, the introduction of the approach also had some troubling effects, for example, by creating top-down accounts of change which spoke more to donor interests than to the ground realities of people affected by these interventions. Ultimately, this paper argues that while a Theory of Change approach can create space for critical reflection, this requires a much broader commitment to learning from individuals, organisations, and the development sector itself.
KerkoCite.ItemAlsoKnownAs: 2339240:PV2LFWGU 2405685:M3EQF58T

Barriers to refugee adolescents' educational access during COVID-19: Exploring the roles of gender, displacement, and social inequalities - Jones, Nicola; Pincock, Kate; Guglielmi, Silvia; Baird, Sarah; Tapia, Ingrid Sanchez; Oakley, Erin; Seager, Jennifer (Journal on Education in Emergencies, 2022)
In this article, we adopt an intersectional conceptual framework to explore the roles gender and other social inequalities have played in shaping adolescents’ access to education during the COVID-19 pandemic. We examine two refugee populations: the Rohingya, who have been excluded from formal education opportunities in Bangladesh, and Syrian refugees in Jordan, who have access [...]Read More...
KerkoCite.ItemAlsoKnownAs: 2339240:KJQ9GDGS 2405685:RKZTB536

OU part of £5.5m research portfolio to improve education tech in low and middle income countries - Grimette, Hannah (OU News, 2022)
The Open University (OU) has launched a study with global research partner, Edtech Hub, to investigate the impact of technology on teaching in Bangladesh. Part of EdTech's first research portfolio, the OU's 3Mpower is one of 13 projects, which represents the largest investment in primary research on EdTech's use in low- and middle-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:M5XGVS2H 2405685:EXXQ3R4B

Focus Country: Kenya (EdTech Hub)
Kenya Focus country EdTech Hub works in six focus countries (Bangladesh, Ghana, Kenya, Pakistan, Sierra Leone and Tanzania) to conduct research, support governments, and support scale-up of EdTech programmes. “Female students with teacher on computer” by Ericsson Images is licensed under CC BY-NC-ND 2.0 READ KENYA COUNTRY SCAN Population: 47.6 million Median age: 20 years Internet penetration: 43% Mobile penetration:…
KerkoCite.ItemAlsoKnownAs: 2339240:DLBNEVSU 2405685:SUZHVA56

Global Education Monitoring Report 2020: Inclusion and Education – All Means All - UNESCO (UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:42XI45XX 2339240:CHMAUW76 2405685:EX9FXZIX 2405685:UGIHX9QY

Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7310489 ZenodoArchiveConcept: 7310488 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7310489 10.53832/edtechhub.0133 2405685:NP52QFM8
Keywords: _r:AddedByZotZen

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Guidance Note 8 Resilient and sustainable energy solutions From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684327 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684327 2339240:J6VCPUDV 2405685:57FXZ5EA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Harnessing EdTech for Neurodivergent Learners in LMICs: A Rapid Evidence Synthesis - Layachi, Aida; Plaut, Daniel (EdTech Hub, 2025)
As neurodivergent learners continue to face multifaceted challenges that affect their education, education systems, environments, and practices have struggled to address their needs adequately. This rapid evidence synthesis explores the current state of evidence regarding the use of educational technologies (EdTech) for neurodivergent learners in low-and middle-income countries (LMICs). The review was conducted in two phases to offer complementary insights on the topic. The first phase presents the findings regarding the use of EdTech for neurodivergent learners in LMICs. The second phase expands the focus, offering evidence and examples that extend beyond LMICs, providing a global perspective on how EdTech could be applied and adapted to LMICs to address different challenges faced by neurodivergent learners. The holistic framework for EdTech for neurodivergence presented in this synthesis provides insights and recommendations regarding the potential of EdTech in optimising systems, environments, and education practices. Keywords: EdTech, Neurodivergence, LMICs, holistic framework, learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15737188 ZenodoArchiveConcept: 15737187 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1124 2405685:WNGITGKP
Keywords: _r:AddedByMyEducationEvidence

Guidance on Distance Learning Modalities to Reach All Children and Youth During School Closures - UNICEF Regional Office for South Asia (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:29QHBJD5 2405685:4TXJ8GQB

Guidance on Distance Learning Modalities to Reach All Children and Youth During School Closures - UNICEF Regional Office for South Asia (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:29QHBJD5 2405685:4TXJ8GQB

Systemic Mixed-Methods Research — A conceptual framework for EdTech research along the IDIA scale - Haßler, Björn; Hennessy, Sara; Hollow, David; Simpson, Lea; Carter, Alice; Damani, Kalifa; Francis, Gill; Jordan, Katy; McIntyre, Nora; Mitchell, Joel (EdTech Hub, 2019)
EdTechHub.Copy: 2129771:SLHSYDRF PreviousDOI: 10.5281/zenodo.3377829 PreviousShortDOI: 10/ghgngc KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3377828 10.5281/zenodo.3377829 10.5281/zenodo.3595482 10/ghgngc 2129771:84AIHEAJ 2129771:Q74CFTXR 2129771:SLHSYDRF 2339240:2DHE9CQC 2339240:BF96YT5K 2339240:FJZA9NPX 2339240:NLMLQD75 2405685:6YT2AIMC 2405685:7S8Z2IUF 2405685:RUSE8WYV
Keywords: LP: English; R:Mixed methods; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; _yl:f; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

BRAC Humanitarian Play Lab Model: Promoting healing, learning and development for displaced Rohingya children - Mariam, Erum; Ahmad, Jahanara; Sarah Sarwar, Sarwat (The Journal on Education in Emergencies, 2021)
In August 2017, almost a million Rohingya people fled to Bangladesh to escape violence and persecution in Myanmar; 55 percent of them were children. BRAC, one of the largest non-governmental organizations in the world, operates an initiative called the Humanitarian Play Lab model for children ages 0-6 in the Rohingya refugee camps in Bangladesh. The intervention combines play-based learning with psychosocial support from para-counselors to promote positive developmental outcomes for children in crisis settings. Designed using a community-based participatory approach that promotes a sense of pride and belonging among those living in a displaced community, the play model strongly emphasizes the importance indigenous cultural practices play in healing and learning. This field note, which describes the key features of the play model, covers the period of implementation from its start in October 2017 up to December 2019. Our intended audience includes policymakers, practitioners, and other advocates for early childhood development and play who are working to promote child development and well-being in humanitarian settings. We offer this description as a case study of how providing play-based learning to children in emergency situations may help mitigate the detrimental long-term effects of displacement and trauma.
Accepted: 2021-06-07T16:23:07Z Publisher: Inter-agency Network for Education in Emergencies (INEE) KerkoCite.ItemAlsoKnownAs: 10.33682/u72g-v5me 2339240:47FJANET 2405685:BJ9FWUPC 5911999:J9NT5DZ2

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
ZenodoArchiveID: 4556925 PreviousDOI: 10.5281/zenodo.3948175 PreviousDOI: 10.5281/zenodo.4477170 PreviousShortDOI: 10/gg7sp2 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948175 10.5281/zenodo.3948174 10.5281/zenodo.3948175 10.5281/zenodo.4477170 10.5281/zenodo.4556925 2339240:6NYL4Q6K 2339240:782897NS 2339240:CQIWZXYK 2339240:FFVXKB6Y 2339240:FH2WAXTQ 2339240:KAWEDEAZ 2339240:L9THHN3N 2339240:P8B4HPZC 2339240:QLA593HB 2339240:T58E6LDA 2339240:T8L6PTRX 2339240:VZBB4HAF 2405685:839AFBBS 2405685:89H7NAA7 2405685:A2II5ZV7 2405685:A49KTEL6 2405685:AT6JS3QN 2405685:CJR7PMKJ 2405685:DEXS2WA8 2405685:FFSBB3JJ 2405685:NQSPAG3I 2405685:RVZFVD7G 2405685:U95XV67E 2405685:WJRBJQBN 2534378:8FA5G2KF
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4917252 10.5281/zenodo.4917252 2339240:G2X4SJI9 2339240:MUSPGK9F 2339240:MVU3QIHM 2339240:NQF22P32 2405685:B2ABXUCR 2405685:D6PWMC4I 2405685:HW7NU96L 2405685:JWIHBL5M 2405685:PXBXCZ29 2405685:YHC5ZPU8
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

The latent digital divide and its drivers in e-learning among Bangladeshi students during the COVID-19 pandemic - Badiuzzaman, Md; Rafiquzzaman, Md; Rabby, Md Insiat Islam; Rahman, Mohammad Mustaneer (Information, 2021)
The devastating COVID-19 pandemic forced academia to go virtual. Educational institutions around the world have stressed online learning programs in the aftermath of the pandemic. However, because of insufficient access to Information Communication Technology (ICT), a substantial number of students failed to harness the opportunity of online learning. This study explores the latent digital divide exhibited during the COVID-19 pandemic while online learning activities are emphasised among students of Bangladesh. It also investigates the digital divide exposure and the significant underlying drivers of the divide. In order to accomplish this, a cross-sectional survey was employed to collect quantitative data, mixed with open-ended questions were utilised to gather qualitative information from the student community. The findings revealed that despite the majority of students having physical access to ICT, only 32.5% of students could attend online classes seamlessly. In total, 34.1% reported data prices as the critical barrier, while 39.8% identified poor network infrastructure as the significant barrier preventing them from participating in online learning activities. Although most students possess physical access to various devices and the Internet, they face the first-level digital divide due to the quality of access and price of cellular Internet. Consequently, they fail to take advantage of physical access, resulting in the third-level digital divide (utility gap), which submerges them into a digital divide cycle. The primary objective of this study is to explore the underlying issues of the digital divide among Bangladeshi students. This will assist relevant stakeholders (e.g., the Bangladesh government, educational institutions, and researchers) to gain necessary insights and theoretical understanding of underlying limitations and emergent directions to arrange adequate support for underprivileged students to undertake essential online learning activities.
Number: 8 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/info12080287 2339240:6S36DZH9 2405685:BTG5QS57
Keywords: COVID-19; digital divide; multi-level digital divide; online learning

Assessing Early Childhood Fluid Reasoning in Low- and Middle-Income Nations: Validity of the Wechsler Preschool and Primary Scale of Intelligence Across Seven MAL-ED Sites - Ruan-Iu, Linda; Pendergast, Laura L.; Rasheed, Muneera; Tofail, Fahmida; Svensen, Erling; Maphula, Angelina; Roshan, Reeba; Nahar, Baitun; Shrestha, Rita; Williams, Brittney; Schaefer, Barbara A.; Scharf, Rebecca; et al. (Journal of Psychoeducational Assessment, 2019)
An adapted version of the Wechsler Preschool and Primary Scale of Intelligence—Third Edition (WPPSI-III) was administered to assess cognitive functioning among 1,253 5-year-old children from the Malnutrition and Enteric Disease (MAL-ED) study—an international, multisite study investigating multiple aspects of child development. In this study, the factor structure and invariance of the WPPSI-III were examined across seven international research sites located in Bangladesh, Brazil, India, Nepal, Pakistan, South Africa, and Tanzania. Using a multiple indicator multiple cause (MIMIC) modeling approach, the findings supported the validity of a fluid reasoning dimension (comprised of block design, matrix reasoning, and picture completion subscales) across each of the seven sites, although the scores were noninvariant. Accordingly, these scores are recommended for research purposes and understanding relationships between variables but not for mean comparisons or clinical purposes.
shortDOI: 10/ggd57h KerkoCite.ItemAlsoKnownAs: 10.1177/0734282919850040 10/ggd57h 2339240:24DRAS7L 2405685:JVQJPXK3

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
ZenodoArchiveID: 4556935 PreviousDOI: 10.5281/zenodo.4476991 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3956366 10.5281/zenodo.3956366 10.5281/zenodo.4476991 10.5281/zenodo.4556935 2259720:BFY7A76P 2339240:3WZUWHB3 2339240:CVI8639W 2339240:G8MSWBJC 2339240:IF3IMDSW 2339240:NUYRVP8T 2339240:UXMEFECL 2405685:BVXSZ7G4 2405685:BZFLWXG6 2405685:DPRU64AB 2405685:FMULV6ZI 2405685:TJ95P4G4 2405685:UJF6X47J 2405685:UVB294JN 2405685:Y3XDX8FW 4803016:WC4XVPPN
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7245945 ZenodoArchiveConcept: 7245944 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7245945 10.53832/edtechhub.0128 2405685:X8MUXS39
Keywords: _r:AddedByZotZen

Evaluation of the Global Education Cluster (GEC) Action (2017-2019): Strengthening Coordination of Education in Emergencies - UNICEF (2020)
This evaluation was conducted between November 2019 and February 2020, with the main purpose of generating learning, for Global Education Cluster (GEC) managers and other stakeholders, on ‘what worked where and how’ in the DG/ECHO grant to the GEC (2017-2019). The evaluation also serves an accountability function by providing an independent assessment of the GEC Action against its intended results. Building on 2 in-depth country case studies in Bangladesh and North East (NE) region of Nigeria, and a broader multi-country case study, through a desk review of relevant documents, key informant interviews and an online survey administered with education cluster/coordination team actors, the report generates findings related to the relevance, effectiveness, efficiency, coordination and connectedness of the grant. The evaluation also produced 5 recommendations, validated through a learning workshop held in Brussels, which informed the process of development of the new GEC strategy (2020-2021).
KerkoCite.ItemAlsoKnownAs: 2339240:PWTLL9UW 2405685:Y5398HMA

Introducing Ostad AI - Al Musabbir, Abdullah (LinkedIn)
🚀 Introducing Ostad AI, an assessment AI tool that can generate questions based on teacher-delivered lectures, check students' answers, and provide accurate feedback. ✅ We have been testing this product for the past 14 days with a group of 704 students enrolled in one of our Live courses. 💥 ✅ 95% of the students were satisfied, and they believed that their instructor had checked the answers 🤭. 5% indicated they needed additional justification for the deduction of points. 🫡 ✅ A student in such course must attend three different sorts of exams every week! 🤝 Being an online live learning platform for Upskilling, it was extremely difficult for us to review every answer sheet in a timely and accurate manner. So, it's a great relief for us now! 🙏 A significant milestones for the Ostad team and also for the Bangladesh's online learning industry. 🚀🚀 #ostad #Livelearning #onlinelearning | 30 comments on LinkedIn
KerkoCite.ItemAlsoKnownAs: 2339240:9848NWZ2 2405685:AQSWFU3I

Assessing the real-life socio-economic scenario of established slums in Dhaka: the cases of Korail and Sattola - Bashar, Raisa; Tonmoy, Sirajus; Ria, Alvira; Khan, Nazmul (European Online Journal of Natural and Social Sciences, 2020)
The research aims to assess the current situation of three primary socioeconomic indicators, namely education, health and water availability at the two most established slums of Bangladesh's capital Dhaka-Korail and Sattola. Surveys, using cluster and then random sampling to target households, and analysis, found that both slums' children's education level was moderate with 52%-68% and 20%-28% availing primary and secondary education, respectively; several NGOs had helped to establish brick-and-mortar latrines and disseminate necessary and effective awareness about sanitation; and surveyed slum dwellers were economically strong, with 68%-70% of the interviewed households' income levels being 10,000-15,000 BDT (USD 118-178) per month. A comparative analysis with national level statistics also yielded that the conditions in these slums are truly better than previously thought. Primary recommendation includes in-depth monitoring to understand why such large numbers live in slums, even though they can afford better.
KerkoCite.ItemAlsoKnownAs: 2405685:Y4FHHY92
Keywords: ⚠️ Invalid DOI

Annual Primary School Census 2019 - MoPME (Directorate of Primary Education, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9X2J5EH3 2405685:TJ73RPSY

Measuring Rohingya Children’s Development: Cultural and Contextual Adaptation of IDELA - Nyeu, Maung; Alif, Ahmed; Tiwari, Priyamvada; Busch, Julian; Tofail, Fahmida; Yoshikawa, Hirokazu (figshare, 2022)
In this brief, NYU Global TIES for Children researchers describe a rapid iterative process of cultural, linguistic, and contextual adaptation and extension of child assessment tools for Rohingya Children in Cox's Bazar, Bangladesh. It includes three specific examples showcasing the rigorous, culturally responsive, equity-based approach to adaptation. This report also highlights some of the most critical findings from using this extended IDELA, known as IDELA-E, in our pilot study. Results suggest that IDELA-E is responsive to the environment in which the Rohingya children grow up and can capture their learning and development gains across multiple domains. Assessment using IDELA-E shows the age-based developmental progression of Rohingya children across these five domains: fine and gross motor, emergent literacy, emergent numeracy, socio-emotional, and executive function development. Overall, this brief highlights a rigorous process of cultural and contextual adaptation of tools for assessing children in a low-resourced context in the global south.
KerkoCite.ItemAlsoKnownAs: 10.6084/m9.figshare.21565404.v1 2339240:44ETW9Z7 2405685:UW87Z7F4

Educational Technology in Developing Countries: A Systematic Review - Rodriguez-Segura, Daniel (University of Virginia, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:3NFUQ2N5 2339240:7X8NJI23 2339240:AAP9R7UD 2339240:TY3PYSTX 2405685:5IRBQ464 2405685:5J25FLQT 2405685:RQ4ND4UQ 2405685:RVLBVG3I 2405685:YLEQ3IT6
Keywords: ___working_potential_duplicate

Using mobile phones to improve educational outcomes: An analysis of evidence from Asia - Valk, John-Harmen; Rashid, Ahmed T.; Elder, Laurent (The International Review of Research in Open and Distributed Learning, 2010)
Despite improvements in educational indicators, such as enrolment, significant challenges remain with regard to the delivery of quality education in developing countries, particularly in rural and remote regions. In the attempt to find viable solutions to these challenges, much hope has been placed in new information and communication technologies (ICTs), mobile phones being one example. This article reviews the evidence of the role of mobile phone-facilitated mLearning in contributing to improved educational outcomes in the developing countries of Asia by exploring the results of six mLearning pilot projects that took place in the Philippines, Mongolia, Thailand, India, and Bangladesh. In particular, this article examines the extent to which the use of mobile phones helped to improve educational outcomes in two specific ways: 1) in improving access to education, and 2) in promoting new learning. Analysis of the projects indicates that while there is important evidence of mobile phones facilitating increased access, much less evidence exists as to how mobiles promote new learning.
shortDOI: 10/gf5f5b KerkoCite.ItemAlsoKnownAs: 10.19173/irrodl.v11i1.794 10/gf5f5b 2339240:F5U9J9FX 2405685:I6IN2PZY 2405685:UM2C54QN
Keywords: distance learning; educational outcomes; information and communication technologies; mobile learning; mobile phones; new learning

Lowering Barriers to Remote Education: Experimental Impacts on Parental Responses and Learning - Beam, Emily; Mukherjee, Priya; Navarro-Sola, Laia (SSRN Electronic Journal, 2022)
We conduct a randomized controlled trial with households of secondary school students in Bangladesh to investigate how parents adjust their investments in response to three educational interventions: an informational campaign about an educational phone application, an internet data subsidy, and oneon-one phone learning support. We find that offering an educational service in a context where other barriers to take-up exist can still trigger parental educational investments by acting as a signal or nudge. These behavioral changes result in lasting learning gains concentrated among richer households, reflecting that the relevant behavior change—increased tutoring investment—is easier for them to implement. In contrast, when interventions do increase take-up, they have the potential to narrow the socioeconomic achievement gap. We observe that increased usage of the targeted educational service limits parental behavioral responses. This implies that learning gains in these cases are directly caused by the potential effectiveness of the services adopted. In our setting, remote one-to-one teacher support improves learning among students from poorer households, whereas receiving the free data package jointly with the app information has no impact on learning.
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.4234910 2339240:Y3YD9HTV 2405685:YFMSGQUG

Lowering Barriers to Remote Education: Experimental Impacts on Parental Responses and Learning - Beam, Emily; Mukherjee, Priya; Navarro-Sola, Laia (2022)
We conduct a randomized controlled trial with households of secondary school students in Bangladesh to investigate how parents adjust their investments in response to three educational interventions: an informational campaign about an educational phone application, an internet data subsidy, and one-on-one phone learning support. We find that offering an educational service in a context where other barriers to take-up exist can still trigger parental educational investments by acting as a signal or nudge. These behavioral changes result in lasting learning gains concentrated among richer households, reflecting that the relevant behavior changeincreased tutoring investmentis easier for them to implement. In contrast, when interventions do increase take-up, they have the potential to narrow the socioeconomic achievement gap. We observe that increased usage of the targeted educational service limits parental behavioral responses. This implies that learning gains in these cases are directly caused by the potential effectiveness of the services adopted. In our setting, remote one-to-one teacher support improves learning among students from poorer households, whereas receiving the free data package jointly with the app information has no impact on learning.
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.4234910 2339240:VTATZW3D 2405685:T9HU5JTI
Keywords: educational inequality; educational technology; human capital; parental investments

Lowering Barriers to Remote Education: Experimental Impacts on Parental Responses and Learning - Beam, Emily; Mukherjee, Priya; Navarro-Sola, Laia (2022)
We conduct a randomized controlled trial with households of secondary school students in Bangladesh to investigate how parents adjust their investments in response to three educational interventions: an informational campaign about an educational phone application, an internet data subsidy, and one-on-one phone learning support. We find that offering an educational service in a context where other barriers to take-up exist can still trigger parental educational investments by acting as a signal or nudge. These behavioral changes result in lasting learning gains concentrated among richer households, reflecting that the relevant behavior changeincreased tutoring investmentis easier for them to implement. In contrast, when interventions do increase take-up, they have the potential to narrow the socioeconomic achievement gap. We observe that increased usage of the targeted educational service limits parental behavioral responses. This implies that learning gains in these cases are directly caused by the potential effectiveness of the services adopted. In our setting, remote one-to-one teacher support improves learning among students from poorer households, whereas receiving the free data package jointly with the app information has no impact on learning.
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.4234910 2339240:VTATZW3D 2405685:T9HU5JTI
Keywords: educational inequality; educational technology; human capital; parental investments

Digital Divide or Digital Provide? Technology, Time Use, and Learning Loss during COVID-19 - Asadullah, M. Niaz; Bhattacharjee, Anindita (The Journal of Development Studies, 2022)
COVID-19 school closure has caused a worldwide shift towards technology-aided home schooling. Given widespread poverty in developing countries, this has raised concerns over new forms of learning inequalities. Using nationwide data on primary and secondary school children in slum and rural households in Bangladesh, we examine how learning time at home during the early months of school closure varies by access to technology at home. Data confirms a significant socio-economic and gender divide in access to TV, smartphone, computer, and internet among rural households. However, the analysis of daily time use data shows only a modest return to a technology in terms of boosting learning time at home. The learning-grade gradient is shallow and insensitive to TV, smartphone, and computer access at home. We also find no evidence that technology access per se helps learning by boosting time spent in online schooling and private supplementary coaching/tutoring. While technology access matters in households where parents act as home tutors, the magnitude of such a complementary effect are not large. The results imply a loss of out-of-school learning time during school closure even in households with technology access. We consider additional hypotheses relating to institutional and socio-economic barriers to home-based learning in developing countries.
Publisher: Routledge _eprint: https://doi.org/10.1080/00220388.2022.2094253 KerkoCite.ItemAlsoKnownAs: 10.1080/00220388.2022.2094253 2405685:4QFIBL3G
Keywords: COVID-19; D10; I21; J22; Q50; home-based education; learning crisis; school closure

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341466 ZenodoArchiveConcept: 7341465 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341466 10.53832/edtechhub.0137 2405685:VVT2BI9M
Keywords: _r:AddedByZotZen

The Politics of Education in Developing Countries: From Schooling to Learning - Hickey, Sam; Hossain, Naomi (Oxford University Press, 2019)
Why have many developing countries that have succeeded in expanding access to education made such limited progress on improving learning outcomes? There is a growing recognition that the learning crisis constitutes a significant dimension of global inequality and also that educational outcomes in developing countries are shaped by political as well as socio-economic and other factors. The Politics of Education in Developing Countries focuses on how politics shapes the capacity and commitment of elites to tackle the learning crisis in six developing countries: Bangladesh, Cambodia, Ghana, Rwanda, South Africa, and Uganda.The problem of education quality is serious across the Global South. The Politics of Education in Developing Countries: From Schooling to Learning deploys a new conceptual framework-the domains of power approach-to show how the type of political settlement shapes the level of elite commitment and state capacity to improving learning outcomes. The domain of education is prone to being highly politicized, as it offers an important source of both rents and legitimacy to political elites, and can be central to paradigmatic elite ideas around nation-building and modernity. Of particular importance is the relative strength of coalitions pushing for access as against those focused on issues of higher quality education. This book concludes with a discussion of entry points and strategies for thinking and working politically in relation to education quality reforms and critical commentaries.
KerkoCite.ItemAlsoKnownAs: 2339240:ZZAYYIKN 2405685:QACRC4YY 4656463:KABW2JXP

Adolescent problematic internet use and parental mediation: A Bangladeshi structured interview study - Chandrima, Rubaiya Matin; Kircaburun, Kagan; Kabir, Humyon; Riaz, Baizid Khoorshid; Kuss, Daria J.; Griffiths, Mark D.; Mamun, Mohammed A. (Addictive Behaviors Reports, 2020)
Internet-related problems such as excessive internet use, problematic internet use (PIU), and internet addiction, are becoming increasingly studied among Bangladeshi adult students, but there has been little research among adolescents. In Bangladesh, there has been no research examining the role of parental mediation in their children's internet use. Therefore, the present structured interview study investigated Bangladeshi adolescent PIU and its associated socio-demographics, internet use behaviors, and the parental mediation role among 350 high school students residing in Dhaka. The results showed that 84 of adolescents (24.0%) were classified as having PIU (cut-off score of ≥ 50 on the Internet Addiction Test) and nine adolescents (2.6%) were classified as having a severe dependency on the internet (cut-off score of >80 on the Internet Addiction Test). According to hierarchical regression analysis, significant PIU correlates included lower academic results, both parents' lower education, mother working outside the home, more than four days' weekly internet use, more than two hours daily internet use, and active mediation. Additionally, internet use behaviors (i.e., internet use locations, devices, purposes, and applications) and parental internet mediation dimensions other than active mediation (i.e., restrictive mediation, active mediation internet safety, monitoring, and technical mediation) were significantly related to PIU in t-tests and correlation analysis respectively. However, they were non-significant in the hierarchical regression analysis when included into equation altogether. The present study's findings will be helpful in developing country-level policymaking decisions and facilitating future research in the country.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.abrep.2020.100288 2339240:JINXJ99U 2405685:39YEHSPC
Keywords: Bangladeshi adolescence; Internet addiction; Internet use behaviors; Parental mediation; Problematic internet use

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Low Cost Mobile Phones for Large Scale Teacher - Walsh, Christopher S; Shaheen, Robina; Power, Tom; Hedges, Claire; Kahtoon, Masuda; Mondol, Sikander (2012)
Education has the power to transform societies and contribute to social and economic development. In this paper we present the mobile technologies used for teacher professional development (TPD) and communicative language teaching in English in Action (EIA). The project aims to assist 25 million people access greater social and economic opportunities through English language teaching and TPD. EIA, in partnership with the Government of Bangladesh, will work with 80,000 teachers through a work-based programme of TPD using audio and visual resources on low cost mobile phones. With access to over 700 audio files aligned with the national textbook English for Today and professional development films that explain and then illustrate successful student-centred English teaching and learning, the project has already documented significant improvement in teachers’ and pupils’ English language competency. This paper provides an account of, and rationale for, the changes in the technologies used across two phases of the project, from the iPod Nano and Touch used in the pilot study with 690 teachers (2009-2010) to the low cost Nokia C1-01 mobile phone with a micro secure digital (SD) being used in upscaling to 12,500 teachers (2012-2014). We argue the low cost alphanumeric mobile phone with micro SD cards provides unprecedented opportunities to both deliver TPD and improve teachers’ and students’ communicative English language skills. The paper considers the unique suitability mobile phones present for resource constrained education systems in developing countries. Simultaneously we highlight the need for further application and research into the use of mobile technologies, not only for large-scale TPD projects, but for a diversity of international development projects and programmes which aim to achieve sustainable change at scale.
KerkoCite.ItemAlsoKnownAs: 2405685:XPZGL85X

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

What-are-countries-that-already-use-remote-learning-doing-and-what-can-we-learn-from-them-EdTechHub.pdf
KerkoCite.ItemAlsoKnownAs: 2405685:NLH4548E

National Strategy for Artificial Intelligence - Information and Communication Technology Division (Government of Bangladesh, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GNRFKRYV 2405685:SZ4BP98U

National Artificial Intelligence Policy 2024 [Draft] - Ministry of Posts, Telecommunications and Information Technology (Government of Bangladesh, 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:CV9H8CJG 2405685:FTZEXZGG

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14727493 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1088 ZenodoArchiveConcept: 14727492
Keywords: _r:AddedByMyEducationEvidence

Education and Covid-19 response: bringing schools and learning back on track - Ahmed, Manzoor; Rahaman, Mostafizur; Hossain, Syed Shahadat; Ahmed, Ghiasuddin (Education Watch/Campaign for Popular Education (CAMPE), 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:G9RHE7L5 2405685:7U3LNXWS

EIA School-based teachers development - Power, Tom; McCormick, Robert; Eyres, Ian (English In Action, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:U389PI47 2405685:GRPSWZKB

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
ZenodoArchiveID: 5652169 previousZenodoArchiveID: 3805843 previousshortDOI: 10/gg7sqk previousDOI: 10.5281/zenodo.3805843 EdTechHub.Copy: 2129771:DQLDNQGU shortDOI: 10/gg7sqk KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3805843 10.5281/zenodo.3805843 10.53832/edtechhub.0023 10/gg7sqk 2129771:DQLDNQGU 2339240:IWW8CJZN 2339240:N5RG3WT2 2339240:QGMNZZER 2405685:53YEZE6A 2405685:933PQ5Q6 2405685:MHEB7LKZ 2405685:WBNK52L7
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7371460 ZenodoArchiveConcept: 7371459 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7371460 10.5281/zenodo.7473922 10.5281/zenodo.7500121 10.53832/edtechhub.0151 2339240:BE2J66WG 2405685:BBAPFKW4 2405685:JHWKC6F4 2405685:P833K7KC 2405685:YLS6YQ3U
Keywords: _r:AddedByZotZen

Technology-Supported Professional Development for Teachers: Lessons from Developing Countries - McAleavy, Tony; Hall-Chen, Alex; Horrocks, Sarah; Riggall, Anna (Education Development Trust, 2018)
This report captures what might be learnt from a selection of the world’s most interesting examples of technology-assisted in-service professional development in lower-income countries and from wider reflections about the potential of technology to enhance the professional learning of teachers.
KerkoCite.ItemAlsoKnownAs: 2339240:CNU2GKRL 2339240:KPPU5Z99 2339240:RNRNDVLK 2339240:S2XT5FSG 2339240:UYNN98AQ 2339240:Z8QK9TIS 2405685:4JNZ9RRF 2405685:58SRHUVT 2405685:CF2KPK7I 2405685:DJG72BUZ 2405685:FXXS4882 2405685:LW3BSKJ4 2405685:ZEBNC5TV 2534378:6GQU9R37 2534378:ARJJXBIL 2534378:TQ4YR37L 2534378:WSS9V2GJ 2534378:XIMVL4RJ
Keywords: Africa; Bangladesh; Blended Learning; C:Low- and middle-income countries; Developing Nations; ERIC; Resources in Education (RIE); Educational Technology; Elementary Education; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; India; Inservice Teacher Education; Kenya; Large Group Instruction; Nigeria; Online Courses; Pakistan; Policymakers; Practitioners; Refugees; Shared Resources and Services; Social Media; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; ⛔ No DOI found

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
ZenodoArchiveID: 4737460 previousDOI: 10.5281/zenodo.4556939 PreviousDOI: 10.5281/zenodo.3958002 PreviousDOI: 10.5281/zenodo.4477168 PreviousShortDOI: 10/ghgnfc Publisher: Zenodo Version Number: 1 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3958002 10.5281/zenodo.3958002 10.5281/zenodo.4477168 10.5281/zenodo.4556939 10.5281/zenodo.4737460 2259720:36F6CWBU 2339240:23GW5XQ8 2339240:6YJ555Q6 2339240:9CAC5BI5 2339240:ABKFKG4Q 2339240:FC5RCEYW 2339240:GCYWZ39Q 2339240:GZYWFIHI 2339240:JMFNCMP8 2339240:L326GM9E 2339240:MQ8QSK5B 2339240:PB295ID7 2339240:Q8QJYXRQ 2339240:TIVTGHAA 2339240:TYYDMDPR 2339240:VFBZXUEM 2339240:VFBZXUEM; 2339240:WVUDHTHF 2405685:4XTHDWDA 2405685:6PE7ANUL 2405685:78VECZYK 2405685:ALEXQL2P 2405685:BLT5KKXG 2405685:C4JLZV3D 2405685:CZBRW85R 2405685:E4TFYPYP 2405685:IV7MEXRW 2405685:NMXFFTIB 2405685:PKS7U5LC 2405685:RTIHY6H8 2405685:S5PCWMRP 2405685:SA26Q7UG 2405685:V7VESTKX 2405685:WR37F768 2405685:YHERHZKV 2405685:YNMUHK9S 2534378:5794CXFP 2534378:5GTJL9K7 4804264:EZB37W4S
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Dhaka: improving living conditions for the urban poor - World Bank (2007)
KerkoCite.ItemAlsoKnownAs: 2339240:N4KX2CI5 2405685:U5Y84Z3H

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6980271 ZenodoArchiveConcept: 6980270 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6980271 10.53832/edtechhub.0109 2405685:HPWRQP7M
Keywords: _r:AddedByZotZen

Continue or reboot? Overarching options for education responses to COVID-19 in low- and middle-income countries - Haßler, Björn (2020)
Björn Haßler, https://opendeved.net/2020/04/15/continue-or-reboot/, 2020-04-15, DOI: 10.5281/zenodo.3753513
EdTechHub.Source: 2129771:MIMJJLN9 shortDOI: 10/ghgk6t KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3753513 10.5281/zenodo.4706085 10/ghgk6t 2129771:AS5ALSKL 2129771:MIMJJLN9 2339240:742PGZ2D 2405685:36KIX7YE 2405685:5IMAIVQY 2405685:696M6DK9 2405685:RAAGIU4Q
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _yl:p; _zenodoETH; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3878423 previousshortDOI: 10/ghgk6n previousshortDOI: 10/ghgk6n previousDOI: 10.5281/zenodo.3878423 previousshortDOI: 10/ghgk6n EdTechHub.Source: 2405685:DS66UGW4 EdTechHub.Source: <this> shortDOI: 10/ghgk6n KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 10.53832/edtechhub.0019 10/ghgk6n 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:4Z5W36SI 2405685:DS66UGW4 2405685:IS587WTH
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6475261 10.53832/edtechhub.0090 2405685:DSG9QF4F 2405685:GBQT3KMA
Keywords: _r:AddedByZotZen

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5849102 10.53832/edtechhub.0071 2339240:5YT7LKSS 2405685:6FN5VTP7 2405685:8UMQILZ9 2405685:GMA7II34 2405685:WEG87IDU
Keywords: _r:AddedByZotZen

Key considerations when developing an ICT in Education strategy - AlSheikh Theeb, Thaer; Chuang, Rachel; Pandit, Sanjana (EdTech Hub, 2022)
This report was commissioned by UNICEF and produced under UNICEF and EdTech Hub’s global partnership, in response to a request from the UNICEF Laos team that was submitted to the EdTech Hub Helpdesk. It presents key considerations on the overarching process to develop an ICT in Education strategy (e.g., components, stakeholders, timelines) and lists examples of other national ICT in Education and EdTech strategies. Keywords: EdTech strategies; ICT in Education strategies An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6676586 10.53832/edtechhub.00100 10.53832/edtechhub.0100 2405685:2XS75XAU
Keywords: _r:AddedByZotZen

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
previousshortDOI: 10/ghgk6v previousDOI: 10.5281/zenodo.3346903 EdTechHub.Source: 2405685:3BG5X7VG EdTechHub.Source: <this> shortDOI: 10/ghgk6v KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3346903 10.53832/edtechhub.0017 10/ghgk6v 2129771:FLGEYF22 2339240:SZ4GSDD6 2405685:3BG5X7VG
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4596486 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4596486 2129771:3CUB9UK6 2339240:3JHAWKKZ 2339240:NHJQTPKC 2339240:R2MHQ7R6 2405685:BTQ4CU7R 2405685:NZUHTJBG 2405685:R4LUIDP5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

COVID-19 response and recovery plan: education sector - Ministry of Primary and Mass Education (Ministry of Education, Government of the People’s Republic of Bangladesh, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:5R6MZFGM 2405685:2GTFI3D5

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4633326 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4633326 2339240:DNCQ88UV 2339240:ILPGZU8E 2339240:SGQPIKMM 2405685:AR7EAIDU 2405685:XBPZPS3P 2405685:YP4V829F 2405685:ZL7H9N8P
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Poverty and violence in Korail slum in Dhaka - Choudhoury, Zahid ul Arefin; Durrat, Fahima; Hussain, Maria; Alam, Mohammad Shaheenur; Andersen, Morten Koch (University of Dhaka Department of Peace and Conflict Studies, DIGNITY and University of Edinburgh Anthropology Department, 2016)
KerkoCite.ItemAlsoKnownAs: 2339240:4WWBJ9J9 2405685:MFAXWBP9

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
previousshortDOI: 10/gg8hqq previousshortDOI: 10/gg8hqq previousDOI: 10.5281/zenodo.3804380 previousshortDOI: 10/gg8hqq EdTechHub.Source: 2405685:UXQG7GRG EdTechHub.Source: <this> shortDOI: 10/gg8hqq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 10.53832/edtechhub.0014 10/gg8hqq 2129771:X82WTVD8 2339240:4X8SH6RY 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:SYLGY9MM 2405685:UXQG7GRG
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:T7BK22I4

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4617798 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4617798 2339240:V3PGSF2W 2405685:EH6F8M5P
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Technology-Enabled Psychosocial Support Interventions for Education in Emergencies - Moustafa, Nariman; Mtungwa, Nothando (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15806037 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1128 ZenodoArchiveConcept: 15806036
Keywords: _r:AddedByMyEducationEvidence

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
ZenodoArchiveID: 4140412 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4140412 2129771:9X3BTTLU 2339240:9PYYNK6J 2405685:ISTFVCA7 2405685:NS927T5K
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Approaches to teacher professional development in low-to-middle-income countries - Power, Tom (Sustainable English language teacher development at scale: Lessons from Bangladesh, 2019)
This chapter begins by situating discussion of approaches to teacher development (TD) in the context of the grand societal challenge of Education for All (UNESCO 2014), as written into the earlier Millennium Development Goals (MDGs) and now Sustainable Development Goal (SDG) 4:‘to ensure inclusive and equitable quality education for all.’ This goal cannot be met without addressing the stark and urgent need for greater numbers of teachers who are adequately equipped with the knowledge and skills to enable effective student learning. Drawing upon personal experiences of work with teachers in LMICs over nearly two decades, the chapter argues against ‘blaming teachers’ for poor student learning outcomes, and advocates instead the development of better understandings of the often challenging contexts in which teachers practise. The chapter then critically examines common approaches to TD that have often failed adequately to equip teachers for classroom practice, outlining a broadly supported agenda for reform. Recent literature has begun to identify certain characteristics of TD programmes that are increasingly associated with effective student outcomes, in what may be an emerging consensus. These characteristics are briefly outlined, before the chapter closes with lessons learned from English in Action. EIA has both contributed to and benefitted from this emerging evidence base and Chapter 5 illustrates how the implementation of EIA exemplifies such characteristics through a cohesive programme design.
Extra URL: http://oro.open.ac.uk/57052/ KerkoCite.ItemAlsoKnownAs: 2339240:D5ABKQWT 2405685:5G9NIHEU 2405685:KJGDVY5F 2405685:P8GU4VUJ 2405685:W9CSF5TT 2534378:3KFFQRC7 2534378:RSWZTN7D
Keywords: Important; Read

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14648336 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1087 ZenodoArchiveConcept: 14648335
Keywords: Hide; _r:AddedByMyEducationEvidence

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
oldDOI: 10.5281/zenodo.6498098 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 10.5281/zenodo.7716253 10.53832/edtechhub.0082 10.53832/edtechhub.0170 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP 2405685:UJWVTSCK
Keywords: _r:AddedByZotZen

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
ZenodoArchiveID: 5652129 previousZenodoArchiveID: 3891379 previousshortDOI: 10/ghgnfv previousDOI: 10.5281/zenodo.3891379 EdTechHub.Source: 2405685:LP4PGMNA shortDOI: 10/ghgnfv KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3891379 10.5281/zenodo.3891379 10.5281/zenodo.4348995 10.53832/edtechhub.0043 10/ghgnfv 2129771:3YH4WC8N 2129771:J35ZR45N 2339240:6VEXVUL7 2339240:CDU93LQU 2339240:CUSR6ZBJ 2339240:FS3CFIBL 2339240:N7RDGZGY 2339240:V229A7WT 2339240:Z4FHRC9L 2405685:4PAZ4ZQH 2405685:8WYASBE4 2405685:KL56SD42 2405685:LP4PGMNA 2405685:S2A2EQQC 2405685:WFMBLBBE 2405685:XIQ5CL9B 2405685:XJ42VUQG 2405685:YY4LI6EI
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (Education Commission, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
shortDOI: 10/ghgk64 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3983877 10/ghgk64 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:7SUZMICK 2339240:BGZYE7EH 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:88MADQ2R 2405685:FPPVW2ZG 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6 2405685:WVC3S4C8
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
shortDOI: 10/ghgk63 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4118177 10/ghgk63 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:BGZYE7EH 2339240:FTULJL3H 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:2G7TFTEB 2405685:F2B8T3ZP 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
previousshortDOI: 10/ghgnf6 previousshortDOI: 10/ghgnf6 previousDOI: 10.5281/zenodo.3406132 previousshortDOI: 10/ghgnf6 EdTechHub.Source: 2405685:KWJRW62J EdTechHub.Source: <this> shortDOI: 10/ghgnf6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3406132 10.5281/zenodo.3406132EdTechHub.ItemAlsoKnownAs: 10.53832/edtechhub.0010 10/ghgnf6 2129771:3H8JIJ9T 2129771:MG4TM5B3 2339240:CN8LY32H 2339240:EG4V9NYX 2339240:T37Q6QE6 2339240:W2B4DTPS 2405685:7EP4VHD7 2405685:B76WDWTE 2405685:KWJRW62J 2405685:QFMSIUXQ 2405685:Y4EVL7PR 2486141:TAPS8LVP
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
ZenodoArchiveID: 4684361 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684361 2339240:SL23268I 2339240:VTWI3GZJ 2405685:UF3XJXGS 2405685:UXHEIEWM 2405685:ZA9RWW28
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5120788 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5120788 10.5281/zenodo.5142473 2405685:3C8VWLJP 2405685:772S7Z4R 2405685:CW2FHVT8
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech for Girls' Education: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; D'Rozario, Jonny; Thinley, Sangay; Mazari, Haani; Hinks, Jessica (EdTech Hub, 2025)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for girls in Southeast Asia. The review summarises how EdTech is currently being used with girls in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech for girls' education. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for girls, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for girls. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987856 ZenodoArchiveConcept: 10987855 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1022 10.53832/edtechhub.1086 2405685:QEHJZIUB 2405685:S4V6PXXU

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0115 2339240:3KZX9ARU 2405685:BBQE9QUM 2405685:UUDK52LQ 2405685:YB52PCMQ
Keywords: ⛔ No INSPIRE recid found

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11235144 ZenodoArchiveConcept: 11235143 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1029 10.53832/edtechhub.1030
Keywords: _r:AddedByMyEducationEvidence

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7373033 ZenodoArchiveConcept: 7373032 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7373033 10.53832/edtechhub.0144 2405685:499UU2BN 2405685:D7VXZW6I
Keywords: _r:AddedByZotZen

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Child-directed Tablet-based Learning: Project Launch, Monitoring, and Improvement Toolkit - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MJ592UKH

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
2339240:7FA4YDWJ 2339240:YBKKN8XE KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5498054 10.5281/zenodo.5498054 2339240:3H4M8YJ8 2339240:5S4BZY48 2339240:SRWI5WQJ 2405685:BCFK4Q23 2405685:JR65CZU2 2405685:JTKTA5X5 2405685:VQ3F9NQ7 2405685:ZLATZSGU 4656463:RIFY2UNL
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Child-directed Tablet-based Learning: Toolkits for project design, preparation, and implementation - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PNMXVDQ2 2405685:A4NNJNSJ 2405685:GBIY52AG

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2339240:SCCGE8HG 2405685:HEXCEXFK 2405685:NBAIXDE4 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2339240:2LWVXYCV 2405685:4CB23ZC6 2405685:AG764A26 2405685:VWJXTPI8
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found